Optical adhesive composition and optical laminate
By using an optical adhesive composition with a (meth)acrylic block copolymer and a colorant with a specific glass transition temperature range, the problems of poor adhesive processability and poor anti-reflection effect in the prior art are solved, and efficient height difference absorption and contrast improvement in Mini/Micro LED display devices are achieved.
Patent Information
- Application Number
- CN202510009780.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2020-03-31
- Filing Date
- 2021-03-26
- Publication Date
- 2025-04-08
AI Technical Summary
In the prior art, there are problems with the processability of the adhesive with low elastic modulus, such as poor shape stability and low handling, and it is difficult to effectively prevent the reflection of metal wiring and the color mixing of RGB when encapsulating the Mini/Micro LED display device.
The (meth)acrylic block copolymer with a specific glass transition temperature range is used as the main component of the optical adhesive composition, and a colorant is combined with the colorant to form an adhesive layer with a high energy storage modulus, which has good processability at room temperature and becomes high fluidity during heating to fully follow the height difference.
It realizes the anti-reflection function and contrast of metal wiring in Mini/Micro LED display device, and has excellent height difference absorption and processability, simplifies the process and improves the manufacturing efficiency.
Smart Images

Figure CN119775919A_ABST
Abstract
Description
[0001] This application is a divisional application of an application with a filing date of March 26, 2021, an application number of 202180025778.6, and an invention name of “Optical Adhesive Composition and Optical Laminate”. Technical Field
[0002] The present invention relates to an optical adhesive composition and an optical laminate suitable for encapsulating a light-emitting element of a self-luminous display device such as Mini / Micro LED. Background Art
[0003] In recent years, self-luminous display devices represented by Mini / Micro LED display devices (Mini / MicroLight Emitting Diode Display, mini / micro light-emitting diode display devices) have been designed as the next generation of display devices. Mini / Micro LED display devices use a substrate with a high density of multiple tiny LED light-emitting elements (LED chips) as a display panel as a basic structure. The LED chips are encapsulated with an encapsulation material and a covering member such as a resin film and a glass plate is laminated on the outermost layer.
[0004] Mini / Micro LED display devices and other self-luminous display devices have several modes, such as white backlight mode, white light-emitting color filter mode, RGB mode, etc. In the white light-emitting color filter mode and RGB mode, in order to prevent the reflection of metal wiring, metal oxides such as ITO, etc. configured on the substrate of the display panel, black packaging materials are sometimes used (for example, see patent documents 1 to 3). Among them, in the RGB mode Mini / Micro LED display device with LED chips arranged, the above-mentioned black packaging material can also help prevent RGB color mixing and improve contrast.
[0005] As the aforementioned black encapsulating material, a liquid curable resin containing a black colorant (dye, pigment) is being used. When using a liquid curable resin containing a black colorant, there is a problem of uneven blackness due to uneven thickness. In addition, compared with dyes, pigments are often selected due to their excellent heat resistance and weather resistance, but in the case of using a liquid curable resin dispersed with a pigment, on the basis of the above-mentioned uneven thickness, there will also be problems such as uneven filling when the liquid curable resin is filled, uneven dispersion of the pigment when flowing, etc. In addition, since the surface of the liquid curable resin that has been solidified after encapsulation does not have a tight fit, it is necessary to use an adhesive or the like to stack the covering components, and there is also a problem of requiring more man-hours and components.
[0006] In order to deal with the problem of uneven blackness, it is possible to consider using an adhesive containing a black colorant. Compared with liquid curable resins, adhesives have lower fluidity, so unevenness caused by thickness, dispersion / sedimentation of pigments, etc. is not easy to occur. In addition, since the adhesive force is maintained even after the LED chip is encapsulated, there is no need to use adhesives to stack covering components, which has the advantage of simplifying work hours and components.
[0007] On the other hand, Mini / Micro LED display devices have LED chips laid out at high density on a substrate, and there are a large number of fine height differences in the gaps between the LED chips. Therefore, the packaging materials used in Mini / Micro LED display devices are required to have the ability to fill the height difference, that is, excellent height difference absorption (also known as "height difference tracking"). In order to improve the above-mentioned height difference absorption, a method of lowering the elastic modulus of the adhesive to improve flexibility is being tried (for example, Patent Document 4).
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Publication No. 2019-204905
[0011] Patent Document 2: Japanese Patent Application Publication No. 2017-203810
[0012] Patent Document 3: Japanese Patent Application No. 2018-523854
[0013] Patent Document 4: International Publication No. WO2016 / 170875 Summary of the invention
[0014] Problem that the invention aims to solve
[0015] Adhesives with low elastic modulus have excellent height difference absorption, but have problems of reduced processability such as shape stability and handling. For example, laminates with adhesive layers with low elastic modulus may suffer from problems such as adhesive shortage during cutting, adhesive layers oozing out from the ends during storage, easy dripping, and foreign matter adhering to the oozing adhesive layers.
[0016] As an adhesive that takes into account both the above-mentioned height difference absorption and processability, a hybrid adhesive is being used. A hybrid adhesive is a stage-cured adhesive that is a mixture of two polymerization initiators and cross-linking agents with different curing start conditions. The hybrid adhesive has the following advantages: first, it has high fluidity, which allows it to be in a semi-cured state with excellent height difference absorption to fully follow the height difference, and then complete the curing, which can improve processability. However, the processability of the adhesive in the semi-cured stage with excellent height difference absorption is low, and there are problems with the handling in the process before the final curing.
[0017] The present invention is conceived based on the above situation, and the purpose of the present invention is to provide an optical adhesive composition that is suitable for manufacturing self-luminous display devices such as Mini / Micro LED display devices that have improved anti-reflection functions and contrast of metal wiring, etc., and has excellent height difference absorption and processability.
[0018] Another object of the present invention is to provide an optical laminate that is suitable for manufacturing self-luminous display devices such as Mini / Micro LED display devices with improved anti-reflection function of metal wiring and contrast, and has excellent height difference absorption and processability.
[0019] Solutions for solving problems
[0020] The inventors of the present invention have conducted in-depth research to achieve the above-mentioned purpose. As a result, it is found that, as a polymer contained in an optical adhesive composition, by using a (meth) acrylic block copolymer having a high Tg segment and a low Tg segment in a specific glass transition temperature range, it will show a high storage modulus near room temperature (e.g., 25°C), hard and good processability, and the storage modulus in the region exceeding 50°C is significantly reduced, becoming highly fluid, and the height difference absorption becomes good. It is also found that by mixing a colorant in the aforementioned (meth) acrylic block copolymer, it is suitable for manufacturing a self-luminous display device with improved anti-reflection function and contrast of metal wiring, etc. The present invention is completed based on these insights.
[0021] That is, a first aspect of the present invention provides an optical adhesive composition characterized in that:
[0022] The optical adhesive composition contains a (meth)acrylic block copolymer and a colorant.
[0023] The (meth)acrylic block copolymer comprises:
[0024] a high Tg segment having a glass transition temperature of 0°C or higher and 100°C or lower, and
[0025] A low Tg segment having a glass transition temperature of -100°C or higher and lower than 0°C,
[0026] The (meth)acrylic block copolymer has tan δ peaks in a region of 0° C. or higher and in a region of lower than 0° C., respectively.
[0027] Here, the glass transition temperature is calculated using the FOX equation from the monomer component composition constituting each segment.
[0028] The optical adhesive composition of the present invention contains a (meth)acrylic block copolymer having the aforementioned high Tg segment and the aforementioned low Tg segment, and having tanδ peaks in the region above 0°C and the region below 0°C, respectively. The aforementioned (meth)acrylic block copolymer undergoes only a transfer / fluidization of the low Tg segment at room temperature (e.g., 25°C) and does not transfer the high Tg segment, so that the (meth)acrylic block copolymer as a whole exhibits a high storage modulus, is hard, and has good processability. In addition, the high Tg segment also transfers / fluidizes in the region above 50°C, and the storage modulus of the (meth)acrylic block copolymer as a whole decreases, resulting in high fluidity.
[0029] When the adhesive layer formed by the optical adhesive composition of the present invention is bonded to a display panel with light-emitting elements (LED chips) arranged at a high density, for example, by bonding under heating conditions such as an autoclave (for example, above 50° C.), high fluidity is formed, so that the fine height difference between the light-emitting elements (LED chips) is fully followed, bubbles are not left, and there is no gap. Then, when the temperature is restored to room temperature (for example, 25° C.) for storage, the storage modulus increases and the processability becomes good.
[0030] In addition, the optical adhesive composition of the present invention further comprises a colorant, which is preferred in the following aspects: the adhesive that seamlessly fills the minute height differences between LED chips prevents reflections caused by metal wiring on the display panel, etc., prevents color mixing between the arranged light-emitting elements (LED chips), and improves contrast.
[0031] In the optical adhesive composition according to the first aspect of the present invention, the maximum value of the peak of tan δ in the region of 0° C. or higher is preferably 0.5 to 3.0. This aspect is preferred in that excellent processability and shape stability of the (meth)acrylic block copolymer can be achieved.
[0032] In the optical adhesive composition according to the first aspect of the present invention, the (meth)acrylic block copolymer is preferably an ABA-type triblock copolymer. This embodiment is suitable in that the (meth)acrylic block copolymer can be easily produced.
[0033] In the ABA type triblock copolymer in the optical adhesive composition of the first aspect of the present invention, it is preferred that the A segment is the high Tg segment and the B segment is the low Tg segment. This embodiment is suitable for achieving the excellent step absorption and processability of the present invention.
[0034] In the optical adhesive composition of the first aspect of the present invention, as a monomer component constituting the aforementioned high Tg segment in the aforementioned (meth)acrylic block copolymer, it is preferred to contain at least one selected from the group consisting of (meth)acrylic acid alkyl esters having a linear alkyl group with a carbon number of 1 to 3, (meth)acrylic acid alkyl esters having a branched alkyl group with a carbon number of 3 or 4, and alicyclic monomers, and more preferably (meth)acrylic acid alkyl esters having a branched alkyl group with a carbon number of 3 or 4. As the aforementioned alicyclic monomer, it is preferred to be a (meth)acrylic acid cycloalkyl ester having a cycloalkyl group with a carbon number of 4 to 10, which may be optionally substituted. This scheme is suitable in the following aspects: controlling so that the aforementioned high Tg segment has a specified glass transition temperature, and the aforementioned (meth)acrylic block copolymer has a tanδ peak in the region above 0°C, so as to achieve the excellent height difference absorption and processability of the present invention.
[0035] In the optical adhesive composition of the first aspect of the present invention, as the monomer component constituting the low Tg segment in the (meth)acrylic block copolymer, it is preferred to contain at least one selected from the group consisting of (meth)acrylic acid alkyl esters having a linear or branched alkyl group with a carbon number of 4 to 18 and hydroxyl-containing monomers. This scheme is suitable in that the low Tg segment is controlled to have a predetermined glass transition temperature, the (meth)acrylic block copolymer has a tanδ peak in a region below 0°C, and the excellent height difference absorption and processability of the present invention are achieved.
[0036] In the optical adhesive composition of the first aspect of the present invention, it is preferred that 1% by weight or more of a hydroxyl-containing monomer is contained relative to the total amount (100% by weight) of the monomer components constituting the low Tg segment in the (meth)acrylic block copolymer. This embodiment is suitable in terms of controlling the glass transition temperature of the low Tg segment to a predetermined value and achieving the excellent height difference absorption and processability of the present invention.
[0037] In the optical adhesive composition of the first aspect of the present invention, the (meth)acrylic block copolymer preferably has a weight average molecular weight of 200,000 or more. This aspect is preferred in that the optical adhesive composition of the present invention can easily obtain good hardness and processability at around room temperature.
[0038] In the optical adhesive composition according to the first aspect of the present invention, it is preferred that the molecular weight distribution of the (meth)acrylic block copolymer is greater than 1 and not more than 5. This aspect is preferred in that the uniformity of the (meth)acrylic block copolymer in the optical adhesive composition according to the present invention is improved, and an adhesive having high transparency is easily obtained.
[0039] In the optical adhesive composition of the first aspect of the present invention, it is preferred that the ratio of the storage modulus at 25°C to the storage modulus at 50°C (storage modulus at 25°C / storage modulus at 50°C) is 3 or more. This embodiment is preferred in the following aspects: in the optical adhesive composition of the present invention, the difference between the storage modulus at room temperature (25°C) and the storage modulus when heated (50°C) is sufficiently enlarged, and it is possible to form high fluidity and show excellent height difference absorption when heated, and harden at room temperature and show excellent processability.
[0040] In the optical adhesive composition of the first aspect of the present invention, it is preferred that the storage modulus at 25°C is 1 MPa or more, and the storage modulus at 50°C is 0.5 MPa or less. This scheme is preferred in the following aspects: in the optical adhesive composition of the present invention, the difference between the storage modulus at room temperature (25°C) and the storage modulus when heated (50°C) is sufficiently enlarged, and it is possible to form high fluidity and show excellent height difference absorption when heated, and harden at room temperature and show excellent processability.
[0041] In the optical adhesive composition of the first aspect of the present invention, it is preferred that the maximum transmittance of the colorant at a wavelength of 400 to 700 nm is 80% or less. This scheme is preferred in that the adhesive that fills the fine height difference between the light-emitting elements (LED chips) without gaps provides sufficient light-shielding properties with respect to visible light, prevents reflection caused by metal wiring on the display panel, etc., prevents color mixing between the arranged light-emitting elements (LED chips), and improves contrast.
[0042] In addition, the second aspect of the present invention provides an adhesive layer formed by the optical adhesive composition of the first aspect of the present invention. In addition, the third aspect of the present invention provides an optical laminate comprising a substrate and an adhesive layer of the second aspect of the present invention. In these schemes, the aforementioned adhesive layer constitutes an encapsulation material for encapsulating the LED chips arranged on the display panel, and the aforementioned substrate constitutes the outermost covering member, so there is no need to stack the covering member separately after encapsulation, which can reduce the number of processes and necessary components, and improve manufacturing efficiency.
[0043] In the optical laminate of the third aspect of the present invention, it is preferred that the surface of the substrate on which the adhesive layer is not laminated is subjected to an anti-reflection treatment and / or an anti-glare treatment. Preferably, the anti-reflection treatment and / or the anti-glare treatment is an anti-glare layer provided on a single side of the substrate. Preferably, the anti-glare layer is formed using an anti-glare layer forming material comprising a resin, particles and a thixotropy imparting agent, and the anti-glare layer is aggregated by the particles and the thixotropy imparting agent, so that the surface of the anti-glare layer has an aggregated portion forming a convex portion. Preferably, in the convex portion on the surface of the anti-glare layer, the average inclination angle θa (°) is in the range of 0.1 to 5.0. These schemes are preferred in the following aspects: giving the surface of the optical laminate of the third aspect of the present invention an anti-reflection function and / or an anti-glare function, preventing the reduction of visibility caused by reflection of external light, image reflection, etc., and adjusting aesthetics such as glossiness.
[0044] The optical laminate of the third aspect of the present invention may further include a surface protection film laminated on the surface of the substrate not laminated with the pressure-sensitive adhesive layer. This aspect is suitable for preventing damage and dirt from attaching during the manufacture, transportation, and shipment of the optical laminate and optical products including the optical laminate.
[0045] In addition, the fourth aspect of the present invention provides a self-luminous display device, the self-luminous display device comprising: a display panel having a plurality of light-emitting elements arranged on a single surface of a substrate, and the optical laminate of the third aspect of the present invention, the surface of the display panel having the light-emitting elements arranged thereon being laminated with the adhesive layer of the optical laminate. In the self-luminous display device of the fourth aspect of the present invention, the display panel may be an LED panel having a plurality of LED chips arranged on a single surface of a substrate. This scheme is preferred in the following aspects: in the self-luminous display device of the fourth aspect of the present invention, the adhesive containing a colorant that fills the fine height difference between the light-emitting elements (LED chips) without gaps can achieve anti-reflection of metal wiring on the substrate, prevent RGB color mixing, and improve contrast.
[0046] Effects of the Invention
[0047] The optical adhesive composition and the optical laminate of the present invention have the above-mentioned structure, so they have excellent height difference absorption and processability and high light shielding property with respect to visible light. Therefore, by using the optical adhesive composition and the optical laminate of the present invention in the manufacture of a self-luminous display device, a self-luminous display device with improved anti-reflection function of metal wiring and contrast can be efficiently manufactured. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 It is a schematic diagram (cross-sectional view) showing one embodiment of the pressure-sensitive adhesive layer of the present invention.
[0049] Figure 2 It is a schematic diagram (cross-sectional view) showing one embodiment of the optical layered body of the present invention.
[0050] Figure 3 This is a schematic diagram (cross-sectional view) showing another embodiment of the optical layered body of the present invention.
[0051] Figure 4 This is a schematic diagram (cross-sectional view) showing another embodiment of the optical layered body of the present invention.
[0052] Figure 5 It is a schematic diagram (cross-sectional view) showing one embodiment of the self-luminous display device (Mini / Micro LED display device) of the present invention.
[0053] Figure 6 It is a schematic diagram (cross-sectional view) showing another embodiment of the self-luminous display device (Mini / Micro LED display device) of the present invention.
[0054] Figure 7 It is a schematic diagram (cross-sectional view) showing another embodiment of the self-luminous display device (Mini / Micro LED display device) of the present invention. DETAILED DESCRIPTION
[0055] [Optical adhesive composition]
[0056] The optical adhesive composition according to the first aspect of the present invention contains a (meth)acrylic block copolymer and a colorant.
[0057] The "optical" in the optical adhesive composition of the first aspect of the present invention refers to use in optical applications, more specifically, use in the manufacture of products (optical products) using optical components, etc. As optical products, for example, image display devices, input devices such as touch screens, etc. can be listed, preferably self-luminous display devices such as Mini / Micro LED display devices and organic EL (electroluminescent) display devices, and in particular, can be suitably used to manufacture Mini / Micro LED display devices. The same is true for the "optical" of the optical laminate of the third aspect of the present invention.
[0058] <(Meth)acrylic block copolymer>
[0059] The (meth)acrylic block copolymer includes a high Tg segment having a glass transition temperature of 0°C to 100°C and a low Tg segment having a glass transition temperature of -100°C to below 0°C, and has tan δ peaks in the region above 0°C and in the region below 0°C.
[0060] In the present specification, a “high Tg segment having a glass transition temperature of 0°C or higher and 100°C or lower” is sometimes referred to as a “high Tg segment”, a “low Tg segment having a glass transition temperature of −100°C or higher and lower than 0°C” is sometimes referred to as a “low Tg segment”, a tan δ peak in the region of 0°C or higher is sometimes referred to as a “high temperature region tan δ peak”, and a tan δ peak in the region of lower than 0°C is sometimes referred to as a “low temperature region tan δ peak”, a (meth)acrylic block copolymer having the high Tg segment, the low Tg segment, the high temperature region tan δ peak, and the low temperature region tan δ peak is sometimes referred to as a “(meth)acrylic block copolymer A”, and an optical adhesive composition containing the (meth)acrylic block copolymer A and a colorant is sometimes referred to as an “optical adhesive composition A”.
[0061] It should be noted that "(meth)acrylic acid" refers to "acrylic acid" and / or "methacrylic acid" (one or both of "acrylic acid" and "methacrylic acid"), and the same applies to the following. In addition, "(meth)acryloyl" refers to "acryloyl" and / or "methacryloyl" (one or both of "acryloyl" and "methacryloyl"), and the same applies to the following.
[0062] The "segment" in the high Tg segment and the low Tg segment refers to a partial structure of each block unit constituting the (meth)acrylic block copolymer A.
[0063] The structure of the (meth) acrylic block copolymer A of the present invention may be a linear block copolymer, a branched (star-shaped) block copolymer or a mixture thereof. The structure of such a block copolymer may be appropriately selected according to the physical properties of the desired block copolymer, and is preferably a linear block copolymer from the perspective of cost and ease of manufacture. In addition, the linear block copolymer may be of any structure (arrangement), and from the perspective of the physical properties of the linear block copolymer or the physical properties of the optical adhesive composition A, it is preferably a block copolymer selected from (AB) n Type, (AB) n -A type (n is an integer greater than 1, for example, an integer from 1 to 3) block copolymer of at least one structure. In these structures, A and B represent segments composed of different monomer compositions. In this specification, the segment represented by A constituting the aforementioned linear block copolymer is sometimes referred to as "A segment", and the segment represented by B is sometimes referred to as "B segment".
[0064] Among these, from the perspective of the physical properties of the manufacturing ease, optical adhesive composition A, etc., it is preferably an AB type diblock copolymer represented by AB, an ABA type triblock copolymer represented by ABA, and more preferably an ABA type triblock copolymer. It is believed that the ABA type triblock copolymer is pseudo-crosslinked by the A segments at both ends, so that the cross-linked structure between the block copolymers becomes a more highly cross-linked structure, and the cohesion of the block copolymer is improved, and higher adhesion (adhesion) can be shown. It should be noted that in an ABA type triblock copolymer, the 2 A segments at both ends may be the same as each other or different.
[0065] In the case where the (meth) acrylic block copolymer A is an ABA type triblock copolymer, at least one of the two A segments and one B segment (a total of 3) is a high Tg segment and at least another is a low Tg segment. From the perspective of the ease of manufacture, the physical properties of the optical adhesive composition A, etc., it is preferred that the A segment is the aforementioned high Tg segment and the B segment is the aforementioned low Tg segment of the ABA type triblock copolymer. In this case, it is preferred that at least one of the two A segments is a high Tg segment and the B segment is an ABA type triblock copolymer of a low Tg segment, and more preferably the two A segments are both high Tg segments and the B segment is an ABA type triblock copolymer of a low Tg segment.
[0066] The glass transition temperature (Tg) of the high Tg segment constituting the (meth) acrylic block copolymer A is, as described above, 0°C or more and 100°C or less. By making the Tg of the high Tg segment in this range, there is a tendency that the storage modulus of the optical adhesive composition A at room temperature (25°C) is easily controlled to be high, hard and excellent in processability, and the storage modulus is significantly reduced in the region exceeding 50°C, becoming a highly fluid adhesive composition. From the perspective of being able to improve the processability of the optical adhesive composition A at room temperature (25°C), the Tg of the high Tg segment is preferably 4°C or more, more preferably 6°C or more, further preferably 8°C or more, further preferably 10°C or more, and particularly preferably 12°C or more. On the other hand, from the perspective that the storage modulus (G') of the optical adhesive composition A is significantly reduced in the region exceeding 50°C and high fluidity is easily formed, the Tg of the high Tg segment is preferably 90°C or less, more preferably 85°C or less, further preferably 60°C or less, further preferably 50°C or less, and particularly preferably 35°C or less.
[0067] As described above, the Tg of the low Tg segment constituting the (meth) acrylic block copolymer A is -100°C or higher and lower than 0°C. By making the glass Tg of the low Tg segment within this range, there is a tendency that only the low Tg segment is fluidized at room temperature (25°C), and appropriate adhesion can be imparted to the optical adhesive composition A while ensuring processability. From the perspective that the storage modulus of the optical adhesive composition A is not easily reduced at room temperature (25°C) and processability can be improved, the Tg of the low Tg segment is preferably -95°C or higher, more preferably -90°C or higher, and further preferably -80°C or higher. On the other hand, from the perspective of being able to improve the appropriate adhesion and processability of the optical adhesive composition A at room temperature (25°C), the Tg of the low Tg segment is preferably -5°C or lower, more preferably -10°C or lower, further preferably -20°C or lower, further preferably -30°C or lower, and particularly preferably -40°C or lower.
[0068] The difference in Tg between the high Tg segment and the low Tg segment constituting the (meth)acrylic block copolymer A (Tg of the high Tg segment - Tg of the low Tg segment) is not particularly limited, but is preferably 30°C or more, more preferably 35°C or more, more preferably 40°C or more, more preferably 45°C or more, further preferably 50°C or more, particularly preferably 55°C or more, preferably 120°C or less, more preferably 115°C or less, more preferably 110°C or less, more preferably 105°C or less, further preferably 100°C or less, and particularly preferably 95°C or less, from the viewpoint that the storage modulus of the optical adhesive composition A at room temperature (25°C) is easily controlled to be high, hard and excellent in processability, and the storage modulus is significantly reduced in the region exceeding 50°C to obtain a highly fluid adhesive composition.
[0069] The glass transition temperature (Tg) of the high Tg segment and the low Tg segment constituting the (meth) acrylic block copolymer A is a calculated glass transition temperature calculated according to the following Fox equation. The calculated glass transition temperature is calculated based on the type and amount of each monomer component constituting the high Tg segment or the low Tg segment of the (meth) acrylic block copolymer A, and therefore can be adjusted by selecting the type and amount of the monomer component of each segment.
[0070] The glass transition temperature (Tg) can be calculated using the following Fox formula [1].
[0071] 1 / Calculate Tg = W1 / Tg(1)+W2 / Tg(2)+…+Wn / Tg(n)[1]
[0072] Here, W1, W2, ...Wn represent the weight fractions (weight %) of monomer component (1), monomer component (2), ...monomer component (n) constituting the copolymer relative to all monomer components, and Tg(1), Tg(2), ...Tg(n) represent the glass transition temperatures (in absolute temperature: K) of the homopolymers of monomer component (1), monomer component (2), ...monomer component (n).
[0073] It should be noted that the glass transition temperature of a homopolymer is known in various documents, product catalogs, etc., and is described, for example, in J. Brandup, EH Immergut, EA Grulke: Polymer Handbook: JOHN WILEY & SONS, INC. For monomers for which no numerical value is described in various documents, values measured by conventional thermal analysis, such as differential thermal analysis, dynamic viscoelasticity measurement, etc., can be used.
[0074] As mentioned above, the temperature region where the high temperature region tanδ peak of the (meth) acrylic block copolymer A appears is 0°C or more (for example, 0°C or more and 100°C or less). By making the high temperature region tanδ peak in this temperature range, there is a tendency that the storage modulus of the optical adhesive composition A at room temperature (25°C) is easily controlled to be high, hard and excellent in processability, and the storage modulus is significantly reduced in the region exceeding 50°C, and it becomes a highly fluid adhesive composition. From the perspective of being able to improve the processability of the optical adhesive composition A at room temperature (25°C), the temperature at which the high temperature region tanδ peak appears is preferably 3°C or more, more preferably 6°C or more, further preferably 9°C or more, further preferably 12°C or more, and particularly preferably 15°C or more. On the other hand, from the perspective that the storage modulus (G') of the optical adhesive composition A in the region exceeding 50°C is significantly reduced and high fluidity is easily formed, the temperature at which the high temperature region tanδ peak appears is preferably 90°C or less, more preferably 80°C or less, further preferably 70°C or less, further preferably 65°C or less, and particularly preferably 60°C or less.
[0075] As described above, the temperature region where the low temperature region tanδ peak of the (meth) acrylic block copolymer A appears is lower than 0°C (e.g., -100°C or higher and lower than 0°C). By making the low temperature region tanδ peak in this temperature range, there is a tendency that only the low Tg segment is fluidized at room temperature (25°C), and appropriate adhesive force can be given to the optical adhesive composition A while ensuring processability. From the perspective that the storage modulus of the optical adhesive composition A is not easily reduced at room temperature (25°C) and processability can be improved, the temperature at which the low temperature region tanδ peak appears is preferably -95°C or higher, more preferably -90°C or higher, further preferably -80°C or higher, and further preferably -70°C or higher. On the other hand, from the perspective of being able to improve the appropriate adhesive force and processability of the optical adhesive composition A at room temperature (25°C), the temperature at which the low temperature region tanδ peak appears is preferably -5°C or lower, more preferably -10°C or lower, further preferably -20°C or lower, further preferably -30°C or lower, and particularly preferably -40°C or lower.
[0076] The maximum value of the tanδ peak in the high temperature region is not particularly limited, but is preferably 0.5 to 3.0. By making the maximum value of the tanδ peak in the high temperature region within this range, it is possible to achieve excellent processability and shape stability of the (meth)acrylic block copolymer, which is preferred in this respect. From the perspective of achieving excellent processability, the maximum value of the tanδ peak in the high temperature region is preferably 0.6 or more, and more preferably 0.7 or more. In addition, from the perspective of not being prone to indentation, the maximum value of the tanδ peak in the high temperature region is preferably 2.5 or less, and more preferably 2.2 or less.
[0077] The maximum value of the tanδ peak in the low temperature region is not particularly limited, but is preferably 0.1 to 2.0. By setting the maximum value of the tanδ peak in the low temperature region to be within this range, it is possible to achieve excellent processability and shape stability of the (meth) acrylic block copolymer, which is preferred in this respect. From the perspective of achieving excellent processability, the maximum value of the tanδ peak in the high temperature region is preferably 0.2 or more, and more preferably 0.3 or more. In addition, from the perspective of not being prone to indentation, the maximum value of the tanδ peak in the low temperature region is preferably 1.5 or less, and more preferably 1 or less.
[0078] It should be noted that the high temperature region tan δ peak and the low temperature region tan δ peak, as well as the temperatures and maximum values at which they appear, are measured by the dynamic viscoelasticity measurement described in the Examples described later.
[0079] The (meth)acrylic block copolymer A is composed of a plurality of segments (including a high Tg segment and a low Tg segment) obtained by polymerizing a monomer component including a monomer (acrylic monomer) having a (meth)acryloyl group in the molecule.
[0080] The (meth)acrylic block copolymer A or each segment thereof preferably contains 70 wt % or more, more preferably 80 wt % or more, particularly preferably 90 wt % or more of the acrylic monomer based on the total amount of the monomer components (100 wt %).
[0081] The acrylic monomer constituting the (meth)acrylic block copolymer A or each segment thereof (including the high Tg segment and the low Tg segment) contains, as the main monomer units having the largest weight proportion, an alkyl acrylate having a linear or branched alkyl group and / or a monomer component derived from an alkyl methacrylate having a linear or branched alkyl group.
[0082] Examples of the (meth)acrylic acid alkyl ester having a linear or branched alkyl group used to form the segments of the (meth)acrylic block copolymer A, i.e., the (meth)acrylic acid alkyl ester having a linear or branched alkyl group contained in the monomer component used to form the aforementioned segments, include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, amyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, and t-butyl (meth)acrylate. Alkyl (meth)acrylates having a linear or branched alkyl group having 1 to 20 carbon atoms, such as 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate. As the alkyl (meth)acrylate used in the above-mentioned segment, one alkyl (meth)acrylate may be used, or two or more alkyl (meth)acrylates may be used. In this embodiment, as the (meth)acrylic acid alkyl ester used for the above-mentioned segment, at least one selected from the group consisting of methyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate, tert-butyl acrylate, hexyl acrylate, heptyl acrylate, octyl acrylate, and isononyl acrylate is preferably used.
[0083] The segments of the (meth)acrylic block copolymer A may contain monomer units derived from alicyclic monomers. As alicyclic monomers used to form the monomer units of the aforementioned segments, i.e., alicyclic monomers contained in the monomer components used to form the segments, for example, (meth)acrylic acid cycloalkyl esters having a cycloalkyl group with 4 to 10 carbon atoms, (meth)acrylic acid esters having a bicyclic hydrocarbon ring, and (meth)acrylic acid esters having a hydrocarbon ring with three or more rings. The aforementioned cycloalkyl group, bicyclic hydrocarbon ring, and hydrocarbon ring with three or more rings may have a substituent. As the substituent, halogen atoms (e.g., fluorine atoms, chlorine atoms, bromine atoms, iodine atoms), linear or branched alkyl groups with 1 to 6 carbon atoms (e.g., methyl, ethyl, n-propyl, isopropyl, etc.) and the like may be cited. There is no particular limitation on the number of the aforementioned substituents, and they may be appropriately selected from 1 to 6. When there are two or more substituents, the two or more substituents may be the same or different.
[0084] Examples of cycloalkyl (meth)acrylates include cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, 3,3,5-trimethylcyclohexyl (meth)acrylate, cycloheptyl (meth)acrylate, and cyclooctyl (meth)acrylate. Examples of (meth)acrylates having a bicyclic hydrocarbon ring include bornyl (meth)acrylate and isobornyl (meth)acrylate. Examples of (meth)acrylates having a tricyclic or higher hydrocarbon ring include dicyclopentyl (meth)acrylate, dicyclopentyloxyethyl (meth)acrylate, tricyclopentyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, and 2-ethyl-2-adamantyl (meth)acrylate. As the alicyclic monomer used in the aforementioned segment, one alicyclic monomer may be used, or two or more alicyclic monomers may be used. In the present embodiment, as the alicyclic monomer used for the above-mentioned segment, a cycloalkyl (meth)acrylate having a cycloalkyl group having 4 to 10 carbon atoms, which may have a substituent (e.g., a linear or branched alkyl group having 1 to 6 carbon atoms), is preferred, and at least one selected from the group consisting of cyclohexyl acrylate and 3,3,5-trimethylcyclohexyl (meth)acrylate is more preferably used.
[0085] The segments of the (meth)acrylic block copolymer A may contain monomer units derived from hydroxyl-containing monomers. Hydroxyl-containing monomers are monomers having at least one hydroxyl group in the monomer unit. When the segments in the (meth)acrylic block copolymer A contain hydroxyl-containing monomer units, adhesion and appropriate cohesion are easily obtained in the optical adhesive composition A.
[0086] As the hydroxyl-containing monomers used to form the monomer units of the aforementioned segments, i.e., the hydroxyl-containing monomers contained in the monomer components used to form the segments, examples thereof include: hydroxyl-containing (meth)acrylates, vinyl alcohol, and allyl alcohol. As the hydroxyl-containing (meth)acrylates, examples thereof include: 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, hydroxyoctyl (meth)acrylate, hydroxydecyl (meth)acrylate, hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl (meth)acrylate. As the hydroxyl-containing monomers used for the aforementioned segments, one hydroxyl-containing monomer may be used, or two or more hydroxyl-containing monomers may be used. In the present embodiment, the hydroxyl-containing monomer used for the aforementioned segment is preferably a hydroxyl-containing (meth)acrylate, and more preferably at least one selected from the group consisting of 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, 4-hydroxybutyl acrylate and 4-hydroxybutyl methacrylate.
[0087] The chain segments of the (meth)acrylic block copolymer A may contain monomer units derived from nitrogen-containing monomers. The nitrogen-containing monomers are monomers having at least one nitrogen atom in the monomer unit. When the chain segments of the (meth)acrylic block copolymer A contain nitrogen-containing monomer units, hardness and good bonding reliability are easily obtained in the optical adhesive composition A.
[0088] Examples of nitrogen-containing monomers used to form the segments, i.e., nitrogen-containing monomers contained in the monomer components used to form the segments, include N-vinyl cyclic amides and (meth)acrylamides. Examples of N-vinyl cyclic amides used as nitrogen-containing monomers include N-vinyl-2-pyrrolidone, N-vinyl-2-piperidone, N-vinyl-3-morpholinone, N-vinyl-2-caprolactam, N-vinyl-1,3-oxazin-2-one, and N-vinyl-3,5-morpholinedione. Regarding (meth)acrylamides as nitrogen atom-containing monomers, for example, (meth)acrylamide, N-ethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, N-n-butyl (meth)acrylamide, N-octyl (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N,N-dipropyl (meth)acrylamide and N,N-diisopropyl (meth)acrylamide. As nitrogen atom-containing monomers for acrylic polymers, one nitrogen atom-containing monomer may be used, or two or more nitrogen atom-containing monomers may be used. In the present embodiment, as the nitrogen atom-containing monomer for the aforementioned segment, N-vinyl-2-pyrrolidone is preferably used.
[0089] The chain segments of the (meth)acrylic block copolymer A may include monomer units derived from carboxyl-containing monomers. Carboxyl-containing monomers are monomers having at least one carboxyl group in the monomer unit. When the chain segments of the (meth)acrylic block copolymer A include carboxyl-containing monomer units, good bonding reliability can sometimes be obtained in the optical adhesive composition A.
[0090] As the carboxyl-containing monomer of the monomer unit for forming the aforementioned segment, i.e., the carboxyl-containing monomer contained in the monomer component for forming the segment, for example, (meth) acrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid and isocrotonic acid can be listed. As the carboxyl-containing monomer for the aforementioned segment, one carboxyl-containing monomer can be used, or two or more carboxyl-containing monomers can be used. In the present embodiment, as the carboxyl-containing monomer for the aforementioned segment, acrylic acid is preferably used.
[0091] Furthermore, as the monomer units for forming the aforementioned segments, monomers other than the above-mentioned alkyl (meth)acrylates, alicyclic monomers, hydroxyl group-containing monomers, nitrogen atom-containing monomers, and carboxyl group-containing monomers (sometimes referred to as "other monomers") can be cited. Examples of other monomers include: alkoxyalkyl (meth)acrylates [e.g., 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, 3-methoxypropyl (meth)acrylate, 3-ethoxypropyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, 4-ethoxybutyl (meth)acrylate, etc.]; epoxy group-containing monomers [e.g., glycidyl (meth)acrylate, methylglycidyl (meth)acrylate, etc.]; Sulfonic acid group-containing monomers [such as sodium vinyl sulfonate, etc.]; phosphoric acid group-containing monomers; (meth)acrylates having aromatic hydrocarbon groups [such as phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, benzyl (meth)acrylate, etc.]; vinyl esters [such as vinyl acetate, vinyl propionate, etc.]; aromatic vinyl compounds [such as styrene, vinyl toluene, etc.]; olefins or dienes [such as ethylene, propylene, butadiene, isoprene, isobutylene, etc.]; vinyl ethers [such as vinyl alkyl ether, etc.]; vinyl chloride, etc.
[0092] The content of other monomers in the monomer units constituting the segments of the (meth)acrylic block copolymer A is not particularly limited as long as it is 30 wt % or less based on the total amount of monomer components (100 wt %) and can be appropriately selected within a range that does not impair the effects of the present invention.
[0093] As the monomer component constituting the high Tg segment of the (meth)acrylic block copolymer A, it is preferred that the monomer component contains a (meth)acrylic acid alkyl ester selected from a group consisting of a (meth)acrylic acid alkyl ester having a linear alkyl group having 1 to 3 carbon atoms (hereinafter sometimes referred to as “(meth)acrylic acid C 1-3 Straight-chain alkyl esters”), (meth)acrylic acid alkyl esters having a branched-chain alkyl group having 3 or 4 carbon atoms (hereinafter sometimes referred to as “(meth)acrylic acid C 3-4 At least one of the group consisting of a branched alkyl ester ("branched alkyl ester") and an alicyclic monomer. The homopolymers of these monomers have a relatively high Tg, so by containing a monomer selected from them as a monomer component constituting a high Tg segment, it is easy to control the Tg of the high Tg segment within the range specified in the present invention.
[0094] The alicyclic monomer is preferably a cycloalkyl (meth)acrylate having a cycloalkyl group having 4 to 10 carbon atoms and optionally having a substituent (e.g., a linear or branched alkyl group having 1 to 6 carbon atoms), more preferably a cycloalkyl (meth)acrylate having a cycloalkyl group having 4 to 10 carbon atoms and optionally having a substituent (e.g., a linear or branched alkyl group having 1 to 6 carbon atoms), and particularly preferably cyclohexyl acrylate (homopolymer Tg: 15° C.) and 3,3,5-trimethylcyclohexyl (meth)acrylate (homopolymer Tg: 52° C.).
[0095] When an alicyclic monomer is contained as a monomer component constituting the high Tg segment, the content of the alicyclic monomer relative to the total amount of the monomer components (100 wt %) is preferably 10 wt % or more (e.g., 10 to 100 wt %), more preferably 20 wt % or more, more preferably 30 wt % or more, more preferably 30 wt % or more, more preferably 40 wt % or more, more preferably 50 wt % or more, more preferably 60 wt % or more, more preferably 70 wt % or more, more preferably 80 wt % or more, more preferably 80 wt % or more, further preferably 90 wt % or more, particularly preferably 95 wt % or more, from the viewpoint of easily controlling the Tg of the high Tg segment within a predetermined range and providing the (meth)acrylic block copolymer A with desired properties.
[0096] As the aforementioned (meth)acrylic acid C 1-3 Straight chain alkyl ester, preferably acrylic acid C 1-3 The linear alkyl ester is particularly preferably methyl acrylate (Tg of the homopolymer: 8°C).
[0097] As the aforementioned (meth)acrylic acid C 3-4 Branched alkyl ester, preferably acrylic acid C 3-4 The branched alkyl ester is particularly preferably tert-butyl acrylate (Tg of the homopolymer: 35°C).
[0098] The monomer component constituting the high Tg segment contains (meth)acrylic acid C 1-3 Straight chain alkyl ester and / or (meth) acrylic acid C 3-4 In the case of branched alkyl esters, (meth)acrylic acid C 1-3 Straight chain alkyl ester and / or (meth) acrylic acid C 3-4 The content of the branched alkyl ester relative to the total amount of the monomer components (100% by weight) is preferably 10% by weight or more (e.g., 10 to 100% by weight), more preferably 20% by weight or more, more preferably 30% by weight or more, more preferably 30% by weight or more, more preferably 40% by weight or more, more preferably 50% by weight or more, more preferably 60% by weight or more, more preferably 70% by weight or more, more preferably 80% by weight or more, more preferably 80% by weight or more, further preferably 90% by weight or more, particularly preferably 95% by weight or more, from the viewpoint of being able to easily control the Tg of the high Tg segment within a predetermined range and to impart desired physical properties to the (meth)acrylic block copolymer A.
[0099] As the monomer component constituting the low Tg segment of the (meth)acrylic block copolymer A, it is preferred that the monomer component contains a (meth)acrylic acid alkyl ester (hereinafter sometimes referred to as “(meth)acrylic acid C ester”) selected from the group consisting of a (meth)acrylic acid alkyl ester having a linear or branched alkyl group having 4 to 18 carbon atoms, from the viewpoint of being able to easily control the Tg of the low Tg segment within a predetermined range and imparting desired physical properties to the (meth)acrylic block copolymer A. 4-18 At least one of the group consisting of (meth)acrylic acid C 4-18 Homopolymers of alkyl esters have a relatively low Tg, so by including them as monomer components constituting the low Tg segments, it is easy to control the Tg of the low Tg segments within the range specified in the present invention. On the other hand, hydroxyl-containing monomers also have a relatively low Tg, and thus, it is easy to obtain adhesion and appropriate cohesion in the (meth)acrylic block copolymer A. Therefore, as a monomer component constituting the low Tg segments of the (meth)acrylic block copolymer A, it is further preferred to include (meth)acrylic acid C 4-18 Both alkyl esters and hydroxyl-containing monomers.
[0100] As the aforementioned (meth)acrylic acid C 4-18 Alkyl esters, preferably acrylic acid C 4-18 Alkyl esters, particularly preferred are butyl acrylate (homopolymer Tg: -55°C), 2-ethylhexyl acrylate (homopolymer Tg: -70°C), n-hexyl acrylate (homopolymer Tg: -57°C), n-octyl acrylate (homopolymer Tg: -65°C), and isononyl acrylate (homopolymer Tg: -58°C).
[0101] The monomer component constituting the low Tg segment contains (meth) acrylic acid C 4-18 In the case of alkyl esters, regarding (meth)acrylic acid C 4-18 The content of the alkyl ester relative to the total amount of the monomer components (100% by weight) is preferably 10% by weight or more (e.g., 10 to 100% by weight), more preferably 20% by weight or more, more preferably 30% by weight or more, more preferably 30% by weight or more, more preferably 40% by weight or more, more preferably 50% by weight or more, more preferably 60% by weight or more, more preferably 70% by weight or more, more preferably 80% by weight or more, more preferably 80% by weight or more, further preferably 90% by weight or more, particularly preferably 95% by weight or more, from the viewpoint of easily controlling the Tg of the low Tg segment within a predetermined range and providing the (meth)acrylic block copolymer A with desired properties.
[0102] As the hydroxyl group-containing monomer, hydroxyl group-containing alkyl (meth)acrylate is preferred, and 4-hydroxybutyl acrylate (homopolymer Tg: -65°C) and 2-hydroxyethyl acrylate (homopolymer Tg: -15°C) are particularly preferred.
[0103] When a hydroxyl-containing monomer is contained as a monomer component constituting the low Tg segment, the content of the hydroxyl-containing monomer relative to the total amount of the monomer component (100% by weight) is preferably 1% by weight or more, more preferably 1.5% by weight or more, more preferably 2% by weight or more, further preferably 2.5% by weight or more, and particularly preferably 3% by weight or more, from the viewpoint of being able to easily control the Tg of the low Tg segment within a predetermined range and being able to impart desired physical properties to the (meth)acrylic block copolymer A. On the other hand, the content of the hydroxyl-containing monomer relative to the total amount of the monomer component (100% by weight) is preferably 50% by weight or less, more preferably 40% by weight or less, more preferably 30% by weight or less, more preferably 20% by weight or less, further preferably 10% by weight or less, and particularly preferably 5% by weight or less.
[0104] The monomer component constituting the low Tg segment of the (meth)acrylic block copolymer A contains (meth)acrylic acid C 4-18 In the case of both alkyl ester and hydroxyl-containing monomer, the hydroxyl-containing monomer and (meth) acrylic acid C 4-18 Alkyl ester ratio (hydroxyl-containing monomer / (meth)acrylic acid C 4-18 The lower limit is preferably 1 / 99, more preferably 1.5 / 98.5, more preferably 2 / 98, further preferably 2.5 / 97.5, and particularly preferably 3 / 97. On the other hand, the upper limit is preferably 50 / 50, more preferably 40 / 60, more preferably 30 / 70, and further preferably 20 / 80.
[0105] The (meth)acrylic block copolymer A can be produced by the living radical polymerization of the above-mentioned monomer components. The living radical polymerization method is preferred in the following aspects: while maintaining the simplicity and versatility of the existing free radical polymerization method, it is not easy to cause termination reaction and chain transfer, and the growth end will not be deactivated and grow, so it is easy to precisely control the molecular weight distribution and produce a polymer with uniform composition.
[0106] In the living radical polymerization method, a high Tg segment can be prepared first and then the monomer of the low Tg segment can be polymerized with the high Tg segment; or a low Tg segment can be prepared first and then the monomer of the high Tg segment can be polymerized with the low Tg segment.
[0107] When the (meth)acrylic block copolymer A is an ABA type triblock copolymer, it is preferred to first produce the A segment and then polymerize the monomer of the B segment with the A segment from the viewpoint of ease of production.
[0108] The living radical polymerization method can be any known method without particular limitation. Depending on the method for stabilizing the polymerization growth end, there are methods such as: a method using a transition metal catalyst (ATRP method); a method using a sulfur-based reversible addition-fragmentation chain transfer agent (RAFT agent) (RAFT method); a method using an organic tellurium compound (TERP method). Among these methods, the RAFT method is preferably used from the perspectives of the diversity of monomers that can be used, the ease of molecular weight control, and the fact that no metal remains in the optical adhesive composition.
[0109] The RAFT method can use a known method without particular limitation, and for example, comprises the following steps: step 1, for example, using a RAFT agent to polymerize a monomer component to prepare a first segment (first RAFT polymerization); and step 2, further adding / polymerizing a monomer component having a different monomer composition from that in step 1 to the first segment obtained in step 1, to add a second segment to the first segment (second RAFT polymerization). After the second RAFT polymerization, the third, fourth, ... RAFT polymerizations are further performed in the same manner as the second RAFT polymerization, and the third, fourth, ... segments can be further added.
[0110] The above-mentioned steps 1 and 2 can be carried out by known and commonly used methods, for example, solution polymerization method, emulsion polymerization method, bulk polymerization method, polymerization method based on heat and active energy ray irradiation (thermal polymerization method, active energy ray polymerization method), etc. Among them, solution polymerization method is preferred in terms of transparency, water resistance, cost, etc. It should be noted that the polymerization is preferably carried out by avoiding contact with oxygen from the perspective of suppressing polymerization inhibition caused by oxygen. For example, it is preferred to carry out the polymerization under a nitrogen atmosphere.
[0111] When the (meth)acrylic block copolymer A is an ABA type triblock copolymer, it is preferably prepared by preparing the A segment in the above step 1 and adding the B segment to the obtained A segment in the above step 2. In this case, the A segment is preferably a high Tg segment and the B segment is preferably a low Tg segment.
[0112] As the RAFT agent, a known substance can be used without particular limitation, and for example, a compound represented by the following formula (1), formula (2), or formula (3) (trithiocarbonate, dithioester, dithiocarbonate) is preferred.
[0113]
[0114]
[0115]
[0116] In formula (1), formula (2), or formula (3) [formula (1) to (3)], R 1a and R 1b are the same or different and represent a hydrogen atom, a hydrocarbon group or a cyano group. 1c represents a hydrocarbon group which may have a cyano group. 1a , R 1b and R 1c Examples of the hydrocarbon group include hydrocarbon groups having 1 to 20 carbon atoms (straight-chain, branched or cyclic saturated or unsaturated hydrocarbon groups, etc.), and hydrocarbon groups having 1 to 12 carbon atoms are preferred. Specific examples of the hydrocarbon group include: methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, cyclohexyl, dodecyl, octadecyl and other straight-chain, branched or cyclic alkyl groups having 1 to 12 carbon atoms; phenyl and other aryl groups having 6 to 12 carbon atoms; benzyl, phenethyl and other arylalkyl groups having a total of 7 to 10 carbon atoms. 1c Examples of the hydrocarbon group having a cyano group include groups in which 1 to 3 hydrogen atoms possessed by the above hydrocarbon groups are substituted with cyano groups.
[0117] In formulas (1) to (3), R 2 It represents a hydrocarbon group or a group in which a part of hydrogen atoms possessed by the hydrocarbon group is replaced by a carboxyl group (for example, a carboxylalkyl group). Examples of the above hydrocarbon group include hydrocarbon groups having 1 to 20 carbon atoms (straight-chain, branched or cyclic saturated or unsaturated hydrocarbon groups, etc.), among which hydrocarbon groups having 1 to 12 carbon atoms are preferred. Specifically, examples of the hydrocarbon group include: methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, cyclohexyl, dodecyl, octadecyl and other straight-chain, branched or cyclic alkyl groups having 1 to 12 carbon atoms; benzyl, phenethyl and other arylalkyl groups having a total carbon number of 7 to 10.
[0118] In the RAFT method, polymerization is carried out by reacting the raw material monomer so as to be inserted between the sulfur atom in the RAFT agent represented by formulas (1) to (3) and the methylene group adjacent to the sulfur atom.
[0119] Most of the above-mentioned RAFT agents are commercially available. Those that are not commercially available can be easily synthesized using known conventional methods. It should be noted that in the present invention, the RAFT agent may be used alone or in combination of two or more.
[0120] Examples of the RAFT agent include trithiocarbonates such as dibenzyl trithiocarbonate and S-cyanomethyl-S-dodecyl trithiocarbonate; dithioesters such as cyanoethyl dithiopropionate, benzyl dithiopropionate, benzyl dithiobenzoate, and acetoxyethyl dithiobenzoate; and dithiocarbonates such as O-ethyl-S-(1-phenylethyl) dithiocarbonate, O-ethyl-S-(2-propoxyethyl) dithiocarbonate, and O-ethyl-S-(1-cyano-1-methylethyl) dithiocarbonate. Among them, trithiocarbonates are preferred, and trithiocarbonates having a bilaterally symmetrical structure in formula (1) are more preferred, and dibenzyl trithiocarbonate and bis{4-[ethyl-(2-acetoxyethyl)carbamoyl]benzyl} trithiocarbonate are particularly preferred.
[0121] The above-mentioned step 1 can be carried out by polymerizing the monomer components in the presence of a RAFT agent. The amount of the RAFT agent used in step 1 is generally 0.05 to 20 parts by weight, preferably 0.05 to 10 parts by weight, relative to 100 parts by weight of the total amount of the monomer components. If such an amount is used, it is easy to control the reaction and also easy to control the weight average molecular weight of the obtained segment.
[0122] The step 2 can be performed by adding monomer components to the polymerization reaction mixture obtained in the step 1 and performing further polymerization.
[0123] The RAFT method is preferably carried out in the presence of a polymerization initiator. As the polymerization initiator, for example, a common organic polymerization initiator can be listed, and specifically, a peroxide and an azo compound can be listed, among which azo compounds are preferred. The polymerization initiator can be used alone or in combination of two or more.
[0124] As a peroxide type polymerization initiator, benzoyl peroxide and t-butyl permaleate are mentioned, for example.
[0125] Examples of the azo compound include 2,2'-azobisisobutyronitrile, 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2-cyclopropylpropionitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2-(carbamoylazo)isobutyronitrile, 2-phenylazo-4-methoxy-2,4 -Dimethylvaleronitrile, 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis(N,N'-dimethyleneisobutylamidine), 2,2'-azobis(isobutylamide) dihydrate, 4,4'-azobis(4-cyanopentanoic acid), 2,2'-azobis(2-cyanopropanol), dimethyl-2,2'-azobis(2-methylpropionate), 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide].
[0126] The amount of the polymerization initiator used is usually 0.001 to 2 parts by weight, preferably 0.002 to 1 part by weight, based on 100 parts by weight of the total amount of the monomer components. If used in such an amount, the weight average molecular weight of the obtained segment can be easily controlled.
[0127] The RAFT method can be a bulk polymerization without using a polymerization solvent, but it is preferred to use a polymerization solvent. Examples of polymerization solvents include aromatic hydrocarbons such as benzene, toluene, and xylene; aliphatic hydrocarbons such as n-pentane, n-hexane, n-heptane, and n-octane; alicyclic hydrocarbons such as cyclopentane, cyclohexane, cycloheptane, and cyclooctane; halogenated hydrocarbons such as chloroform, carbon tetrachloride, 1,2-dichloroethane, and chlorobenzene; ethers such as diethyl ether, diisopropyl ether, 1,2-dimethoxyethane, dibutyl ether, tetrahydrofuran, dioxane, anisole, phenethyl ether, and diphenyl ether; esters such as ethyl acetate, propyl acetate, butyl acetate, and methyl propionate; ketones such as acetone, methyl ethyl ketone, diethyl ketone, methyl isobutyl ketone, and cyclohexanone; amides such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; nitriles such as acetonitrile and benzonitrile; sulfoxides such as dimethyl sulfoxide and cyclopentane. The polymerization solvent may be used alone or in combination of two or more.
[0128] The amount of the polymerization solvent used is not particularly limited, but is preferably 0.01 mL or more, more preferably 0.05 mL or more, further preferably 0.1 mL or more, and preferably 50 mL or less, more preferably 10 mL or less, further preferably 1 mL or less, for example, relative to 1 g of the monomer component.
[0129] The reaction temperature under the RAFT method is usually 60 to 120° C., preferably 70 to 110° C., and is usually carried out under an inert gas atmosphere such as nitrogen. The reaction can be carried out under any conditions of normal pressure, pressurization and reduced pressure, and is usually carried out under normal pressure. In addition, the reaction time is usually 1 to 20 hours, preferably 2 to 14 hours.
[0130] The polymerization reaction conditions of the RAFT method described above can be applied to step 1 and step 2, respectively.
[0131] After the polymerization reaction is completed, the target (meth)acrylic block copolymer A can be isolated by removing the used solvent and residual monomers from the obtained reaction mixture by conventional separation and purification means.
[0132] When the high Tg segment or low Tg segment of the (meth)acrylic block copolymer A is prepared in the above step 1, the weight average molecular weight (Mw) of the high Tg segment or low Tg segment is not particularly limited, but is preferably 10,000 to 1,000,000, more preferably 50,000 to 500,000, and further preferably 100,000 to 300,000. The Mw of the high Tg segment or low Tg segment within this range is suitable for the above-mentioned effect of the present invention.
[0133] When two or more high Tg segments or low Tg segments exist in the (meth)acrylic block copolymer A, the above-mentioned Mw is the sum of the Mw thereof.
[0134] The weight average molecular weight (Mw) of the (meth)acrylic block copolymer A is not particularly limited, but is preferably 200,000 or more, more preferably 300,000 to 5,000,000, and even more preferably 400,000 to 2,500,000. The Mw of the (meth)acrylic block copolymer A within this range is suitable for the effects of the present invention.
[0135] The molecular weight distribution (Mw / Mn) of the (meth)acrylic block copolymer A is not particularly limited, but is preferably greater than 1, more preferably 1.5 or more, further preferably 2 or more, particularly preferably 2.5 or more, and preferably 5 or less, more preferably 4.5 or less, further preferably 4 or less, and particularly preferably 3.5 or less.
[0136] In addition, the said weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) are measured by the GPC method described in the Example mentioned later.
[0137] The content of the high Tg segment in the (meth)acrylic block copolymer A is preferably 10 wt% or more, more preferably 20 wt% or more, further preferably 25 wt% or more, particularly preferably 30 wt% or more, and is preferably 95 wt% or less, more preferably 90 wt% or less, further preferably 85 wt% or less, based on 100 wt% of the entire (meth)acrylic block copolymer A.
[0138] The content of the low Tg segment in the (meth)acrylic block copolymer A is preferably 5 wt% or more, more preferably 10 wt% or more, further preferably 15 wt% or more, and is preferably 60 wt% or less, more preferably 50 wt% or less, further preferably 40 wt% or less, and particularly preferably 30 wt% or less, based on 100 wt% of the entire (meth)acrylic block copolymer A.
[0139] The low Tg segment and the content of the low Tg segment or the ratio thereof within the above range are suitable for the above-mentioned effects of the present invention.
[0140] The content of each segment and their ratio can be calculated based on the weight average molecular weight (Mw) of each segment or (meth)acrylic block copolymer A obtained in each step of the RAFT method, and can be controlled by the addition ratio of monomers when forming each segment and the polymerization rate of each monomer.
[0141] The content of the (meth)acrylic block copolymer A in the optical adhesive composition A is not particularly limited. From the perspective of obtaining excellent processability at room temperature (25°C) and excellent height difference absorption in a region above 50°C, the content is preferably 50% by weight or more (for example, 50 to 100% by weight), more preferably 60% by weight or more, further preferably 80% by weight or more, and particularly preferably 90% by weight or more, relative to the total amount of the optical adhesive composition A (total weight, 100% by weight).
[0142] <Colorant>
[0143] The optical adhesive composition of the first aspect of the present invention contains a colorant. The aforementioned optical adhesive composition A contains a colorant, thereby reducing the transmittance to visible light. By utilizing the adhesive layer formed by the aforementioned optical adhesive composition with reduced transmittance to visible light, the fine height difference between the metal wiring layer and the light-emitting element (LED chip) of the self-luminous display device (Mini / Micro LED display device) is seamlessly encapsulated, and reflections caused by metal wiring, etc. can be prevented, and color mixing of the light-emitting element (LED chip) can be prevented, and the contrast of the image is improved.
[0144] As long as the colorant is soluble or dispersible in the optical adhesive composition, it can be a dye or a pigment. From the perspective that a small amount of addition can achieve low haze and is easy to be evenly distributed without sedimentation like a pigment, a dye is preferred. In addition, from the perspective of obtaining high color rendering even with a small amount of addition, a pigment is also preferred. In the case of using a pigment as a colorant, a pigment with low or no conductivity is preferred. In addition, in the case of using a dye, it is preferably used in combination with an antioxidant described later.
[0145] As the colorant, any colorant that is permeable to ultraviolet light (wavelength 330 to 400 nm) or absorptive to ultraviolet light can be used without limitation as long as it absorbs visible light (wavelength 400 to 700 nm). The transmittance of the colorant is measured using a solution or dispersion diluted with an appropriate solvent or dispersion medium (organic solvent with low absorption in the range of wavelength 330 to 700 nm) such as tetrahydrofuran (THF) so that the transmittance at a wavelength of about 400 nm is 50 to 60%.
[0146] The maximum value of the transmittance of the colorant at a wavelength of 400 to 700 nm (visible light region) may be, for example, 80% or less, 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, 20% or less, 10% or less, or 5% or less. In addition, the average transmittance of the colorant at a wavelength of 400 to 700 nm (visible light region) may be, for example, 80% or less, 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, 20% or less, 10% or less, or 5% or less.
[0147] Examples of ultraviolet-transmitting black pigments include "9050BLACK" and "UVBK-0001" manufactured by TOKUSHIKI CO., Ltd. Examples of ultraviolet-absorbing black dyes include "VALIFAST BLACK 3810" and "NUBIAN Black PA-2802" manufactured by ORIENT CHEMICAL INDUSTRIES CO., LTD. Examples of ultraviolet-absorbing black pigments include carbon black and titanium black.
[0148] The content of the colorant in the optical adhesive composition is, for example, about 0.01 to 20 parts by weight relative to 100 parts by weight of the total amount of monomers used in the preparation of the (meth)acrylic block copolymer A, and can be appropriately set according to the type of the colorant, the color tone of the adhesive layer, the light transmittance, etc. The colorant can be added to the composition as a solution or dispersion dissolved or dispersed in an appropriate solvent.
[0149] In the optical adhesive composition A, in addition to the (meth) acrylic block copolymer A and the colorant, additives may be included within the scope of not damaging the effect of the present invention. As such additives, for example, polymerization initiators, silane coupling agents, solvents, crosslinking accelerators, tackifying resins (rosin derivatives, polyterpene resins, petroleum resins, oil-soluble phenols, etc.), antioxidants, fillers, ultraviolet absorbers, antioxidants, chain transfer agents, plasticizers, softeners, surfactants, antistatic agents, rust inhibitors, etc. It should be noted that the additives may be used alone or in combination of two or more.
[0150] Examples of the polymerization initiator include photopolymerization initiators (photoinitiators), thermal polymerization initiators, etc. The polymerization initiator may be used alone or in combination of two or more. It should be noted that since the adhesive layer formed by the optical adhesive composition A has sufficient shape stability, it may not contain a polymerization initiator.
[0151] The photopolymerization initiator is not particularly limited, and examples thereof include benzoin ether photopolymerization initiators, acetophenone photopolymerization initiators, α-ketol photopolymerization initiators, aromatic sulfonyl chloride photopolymerization initiators, photoactive oxime photopolymerization initiators, benzoin photopolymerization initiators, benzyl photopolymerization initiators, benzophenone photopolymerization initiators, ketal photopolymerization initiators, and thioxanthone photopolymerization initiators.
[0152] Examples of the benzoin ether photopolymerization initiator include benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 2,2-dimethoxy-1,2-diphenylethane-1-one, and anisole methyl ether. Examples of the acetophenone photopolymerization initiator include 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexyl phenyl ketone, 4-phenoxydichloroacetophenone, and 4-(tert-butyl)dichloroacetophenone. Examples of the α-keto alcohol photopolymerization initiator include 2-methyl-2-hydroxypropiophenone and 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropane-1-one. Examples of the aromatic sulfonyl chloride photopolymerization initiator include 2-naphthalenesulfonyl chloride. Examples of the photoactive oxime-based photopolymerization initiator include 1-phenyl-1,1-propanedione-2-(O-ethoxycarbonyl)-oxime. Examples of the benzoin-based photopolymerization initiator include benzoin. Examples of the benzyl-based photopolymerization initiator include benzyl. Examples of the benzophenone-based photopolymerization initiator include benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, polyvinylbenzophenone, α-hydroxycyclohexylphenylketone, and the like. Examples of the ketal-based photopolymerization initiator include benzyldimethylketal, and the like. Examples of the thioxanthone-based photopolymerization initiator include thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, and dodecylthioxanthone.
[0153] The amount of the photopolymerization initiator used is not particularly limited, but is preferably 0.01 to 1 part by weight, more preferably 0.05 to 0.5 part by weight, based on 100 parts by weight of the monomer components constituting the (meth)acrylic block copolymer A.
[0154] Examples of the thermal polymerization initiator include azo polymerization initiators, peroxide polymerization initiators (e.g., dibenzoyl peroxide, tert-butyl permaleate, etc.), redox polymerization initiators, etc. Among them, azo polymerization initiators are preferred. Examples of the azo polymerization initiator include 2,2'-azobisisobutyronitrile, 2,2'-azobis-2-methylbutyronitrile, 2,2'-azobis(2-methylpropionic acid) dimethyl ester, and 4,4'-azobis-4-cyanovaleric acid.
[0155] The amount of the azo polymerization initiator used is not particularly limited, but is preferably 0.05 to 0.5 parts by weight, more preferably 0.1 to 0.3 parts by weight, based on 100 parts by weight of the monomer components constituting the (meth)acrylic block copolymer A.
[0156] The optical adhesive composition A may contain a silane coupling agent within a range that does not impair the effects of the present invention. If the optical adhesive composition A contains a silane coupling agent, the bonding reliability to glass (particularly the bonding reliability to glass under a high temperature and high humidity environment) is improved, which is preferred.
[0157] The silane coupling agent is not particularly limited, and preferably includes: γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-phenyl-aminopropyltrimethoxysilane, etc. Among them, γ-glycidoxypropyltrimethoxysilane is preferred. In addition, as a commercial product, for example, the trade name "KBM-403" (manufactured by Shin-Etsu Chemical Co., Ltd.) can be listed. It should be noted that the silane coupling agent can be used alone or in combination of two or more.
[0158] The content of the silane coupling agent in the optical adhesive composition A is not particularly limited, but is preferably 0.01 to 1 part by weight, more preferably 0.03 to 0.5 part by weight, based on 100 parts by weight of the (meth)acrylic block copolymer A.
[0159] In addition, the optical adhesive composition A may contain a solvent. The solvent is not particularly limited, and examples thereof include organic solvents such as esters such as ethyl acetate and n-butyl acetate; aromatic hydrocarbons such as toluene and benzene; aliphatic hydrocarbons such as n-hexane and n-heptane; alicyclic hydrocarbons such as cyclohexane and methylcyclohexane; and ketones such as methyl ethyl ketone and methyl isobutyl ketone. It should be noted that the solvent may be used alone or in combination of two or more.
[0160] The optical adhesive composition A may be an adhesive composition having any form, for example, an emulsion type, a solvent type (solution type), a hot melt type (hot melt type), etc. Among them, the optical adhesive composition A is preferably a solvent type adhesive composition.
[0161] There is no particular limitation on the method for preparing the optical adhesive composition A, and known methods may be cited, for example. For example, a solvent-based optical adhesive composition A is prepared by mixing a (meth)acrylic block copolymer A, a solvent, and optionally added components (such as the aforementioned silane coupling agent, solvent, additives, etc.).
[0162] The storage modulus (G'25) of the optical adhesive composition A at 25°C is not particularly limited. From the viewpoint of improving processability at room temperature, it is preferably 1 MPa or more, more preferably 1.5 MPa or more, more preferably 2 MPa or more, more preferably 2.5 MPa or more, more preferably 3 MPa or more. From the viewpoint of improving adhesion reliability at room temperature, it is preferably 50 MPa or less, more preferably 45 MPa or less, more preferably 40 MPa or less, more preferably 35 MPa or less, and more preferably 30 MPa or less.
[0163] The storage modulus (G'50) of the optical adhesive composition A at 50°C is not particularly limited. From the viewpoint of improving the height difference absorbency in the region exceeding 50°C, it is preferably 0.5 MPa or less, more preferably 0.45 MPa or less, more preferably 0.4 MPa or less, more preferably 0.35 MPa or less, more preferably 0.3 MPa or less, and from the viewpoint of improving the operability in the region exceeding 50°C, it is preferably 0.0001 MPa or more, more preferably 0.0005 MPa or more, more preferably 0.001 MPa or more, more preferably 0.005 MPa or more, more preferably 0.01 MPa or more.
[0164] The ratio of the storage modulus at 25°C to the storage modulus at 50°C (G'25 / G'50) of the optical adhesive composition A is not particularly limited, but is preferably 3 or more, more preferably 5 or more, more preferably 10 or more, further preferably 15 or more, and particularly preferably 20 or more from the viewpoint of improving processability at room temperature and improving height difference absorption in a region exceeding 50°C. From the viewpoint of adhesion reliability, workability, etc., it is preferably 100 or less, more preferably 95 or less, more preferably 90 or less, further preferably 85 or less, and particularly preferably 80 or less.
[0165] The storage modulus at 25° C. (G′25), the storage modulus at 50° C. (G′25), and their ratio (G′25 / G′50) are measured by the dynamic viscoelasticity measurement described in the examples described below.
[0166] Hereinafter, embodiments of the present invention will be described with reference to the drawings, but the present invention is not limited thereto and is merely illustrative.
[0167] [Adhesive layer]
[0168] The pressure-sensitive adhesive layer of the second aspect of the present invention is formed from the optical pressure-sensitive adhesive composition A. In this specification, the pressure-sensitive adhesive layer formed from the optical pressure-sensitive adhesive composition A may be referred to as "pressure-sensitive adhesive layer A". Figure 1 Schematic diagram (cross-sectional view) showing one embodiment of the adhesive layer A of the second aspect of the present invention. Figure 1 In the figure, 2 is the adhesive layer A, and S1 and S2 are release films.
[0169] The adhesive layer 2 (adhesive layer A) may be provided with release films (isolation films) S1 and S2 on the adhesive surface until use. There is no particular limitation on the form in which the adhesive surface of the adhesive layer 2 is protected by the release films S1 and S2. It may be a form in which two release films S1 and S2 protect each adhesive surface, or it may be a form in which each adhesive surface is protected by one release film with both sides being release surfaces by being wound into a roll. The release films S1 and S2 are used as protective materials for the adhesive layer 2 and are peeled off when attached to an adherend. It should be noted that, in the adhesive layer 2, the release films S1 and S2 also serve as a support for the adhesive layer 2. It should be noted that the release films S1 and S2 do not necessarily have to be provided.
[0170] The adhesive layer A is not particularly limited, and is formed by applying (coating) the optical adhesive composition A on a suitable support such as a substrate, a release film, and heating and drying and / or curing as needed. For example, when the optical adhesive layer A is formed from a solvent-based optical adhesive composition A, the optical adhesive composition A is applied (coated) on a support and heated and dried. The adhesive surface formed after heating and drying can be protected with a release film or the like.
[0171] As the above-mentioned release film, there is no particular limitation, and for example, there can be listed: a substrate with a release treatment layer, a low-adhesive substrate formed by a fluoropolymer, a low-adhesive substrate formed by a non-polar polymer, etc. As the substrate with the above-mentioned release treatment layer, for example, there can be listed: plastic films, papers, etc. that have been surface-treated using release treatment agents such as silicones, long-chain alkyls, fluorines, and molybdenum sulfide. As fluorine-based polymers in the low-adhesive substrate formed by the above-mentioned fluoropolymer, for example, there can be listed: polytetrafluoroethylene, polytrifluorochloroethylene, polyvinyl fluoride, polyvinylidene fluoride, tetrafluoroethylene-hexafluoropropylene copolymer, chlorofluoroethylene-vinylidene fluoride copolymer, etc. In addition, as the above-mentioned non-polar polymer, for example, olefin resins (such as polyethylene, polypropylene, etc.) can be listed. It should be noted that the above-mentioned isolation film is formed by a well-known and commonly used method. In addition, the thickness of the isolation film, etc., is not particularly limited.
[0172] It should be noted that a known coating method can be used during the above-mentioned coating (applying). For example, a conventional coater can be used, specifically a gravure roll coater, a reverse roll coater, a lick coater, a dip roll coater, a rod coater, a knife coater, a spray coater, a comma coater, a direct coater, etc.
[0173] The gel fraction of adhesive layer A is 50 to 90% by weight, preferably 50 to 80% by weight, and more preferably 50 to 70% by weight. By making the gel fraction below 90% by weight, the cohesive force of adhesive layer A is reduced to a certain extent, and adhesive layer A becomes soft, so that the adhesive layer becomes easy to follow the height difference part, and excellent height difference absorption can be obtained. On the other hand, by making the gel fraction above 50% by weight, the problem of the adhesive layer becoming too soft and reducing the processability of the adhesive sheet can be suppressed. In addition, under high temperature environment and high temperature and high humidity environment, the generation of bubbles and floating can be suppressed, and the bonding reliability is improved. The gel fraction can be controlled, for example, by the type, content (amount) of the above-mentioned cross-linking agent.
[0174] The gel fraction (ratio of solvent-insoluble components) can be determined as ethyl acetate-insoluble components. Specifically, it is determined as the weight fraction (unit: weight %) of the insoluble components after the adhesive layer is immersed in ethyl acetate at room temperature (23° C.) for 7 days relative to the sample before immersion. More specifically, the gel fraction refers to a value calculated using the following "Method for Determining Gel Fraction".
[0175] (Method for measuring gel fraction)
[0176] Take about 1g of the adhesive layer, measure its weight, and record this weight as "the weight of the adhesive layer before immersion". Then, immerse the taken adhesive layer in 40g of ethyl acetate for 7 days, recover all the components insoluble in ethyl acetate (insoluble part), dry the recovered insoluble part at 130°C for 2 hours to remove the ethyl acetate, and measure its weight, which is recorded as "the dry weight of the insoluble part" (the weight of the adhesive layer after immersion). Then, substitute the obtained value into the following formula for calculation.
[0177] Gel fraction (weight %) = [(dry weight of insoluble portion) / (weight of adhesive layer before immersion)] × 100
[0178] The melting point of the adhesive layer A is not particularly limited, but is preferably -60 to 20° C., more preferably -40 to 10° C., and further preferably -30 to 0° C. If the melting point is higher than 20° C., adhesive strength cannot be exhibited at room temperature.
[0179] The melting point is not particularly limited, and can be measured, for example, by using the adhesive layer as a sample for measurement by differential scanning calorimetry (DSC) in accordance with JIS K 7121. Specifically, for example, the measurement device can be a "Q-2000" manufactured by TAinstruments, and the temperature can be increased from -80°C to 80°C at a temperature increase rate of 10°C / min.
[0180] There is no particular limitation on the thickness of the adhesive layer A containing a colorant, and it can be appropriately set to be above the height of the light-emitting element in such a way that the light-emitting element arranged on the display panel described later can be fully encapsulated. For example, the thickness of the adhesive layer A containing a colorant is adjusted to 1.0 to 4.0 times, preferably 1.1 to 3.0 times, more preferably 1.2 to 2.5 times, and further preferably 1.3 to 2.0 times the height of the light-emitting element. By making the above thickness more than 1.0 times, the adhesive layer A becomes easy to follow the height difference, and the height difference absorption is improved. In addition, by making the above thickness less than 4.0, the adhesive layer A is not easily deformed, and the processability is improved.
[0181] The thickness of the adhesive layer A containing a colorant is, for example, about 10 to 500 μm, and can be 20 μm or more, 30 μm or more, 40 μm or more, or 50 μm or more. The thickness of the adhesive layer A containing a colorant is 400 μm or less, and can be 300 μm or less, 250 μm or less, or 200 μm or less. By making the above-mentioned thickness more than 10 μm, the adhesive layer A becomes easy to follow the height difference part, and the height difference absorption is improved. In addition, by making the above-mentioned thickness less than 500 μm, the adhesive layer A is not easy to deform, and the processability is improved.
[0182] The average transmittance of the colorant-containing adhesive layer A at a wavelength of 400 to 700 nm (visible light region) is, for example, 80% or less, and can be 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, 20% or less, or 10% or less.
[0183] The maximum transmittance of the adhesive layer A containing the colorant at a wavelength of 400 to 700 nm (visible light region) is, for example, 80% or less, and can be 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, 20% or less, or 10% or less.
[0184] The storage modulus (G'25) of the adhesive layer A at 25°C is not particularly limited. From the perspective of improving processability at room temperature, it is preferably 1 MPa or more, more preferably 1.5 MPa or more, more preferably 2 MPa or more, more preferably 2.5 MPa or more, more preferably 3 MPa or more. From the perspective of improving adhesion reliability at room temperature, it is preferably 50 MPa or less, more preferably 45 MPa or less, more preferably 40 MPa or less, more preferably 35 MPa or less, and more preferably 30 MPa or less.
[0185] The storage modulus (G'50) of the adhesive layer A at 50°C is not particularly limited. From the perspective of improving the height difference absorbency in the region exceeding 50°C, it is preferably 0.5 MPa or less, more preferably 0.45 MPa or less, more preferably 0.4 MPa or less, more preferably 0.35 MPa or less, more preferably 0.3 MPa or less. From the perspective of improving the operability in the region exceeding 50°C, it is preferably 0.0001 MPa or more, more preferably 0.0005 MPa or more, more preferably 0.001 MPa or more, more preferably 0.005 MPa or more, more preferably 0.01 MPa or more.
[0186] The ratio of the storage modulus at 25°C to the storage modulus at 50°C of the adhesive layer A (G'25 / G'50) is not particularly limited. From the perspective of improving processability at room temperature and improving height difference absorption in a region exceeding 50°C, it is preferably 3 or more, more preferably 5 or more, more preferably 10 or more, further preferably 15 or more, and particularly preferably 20 or more. From the perspective of adhesion reliability, operability, etc., it is preferably 100 or less, more preferably 95 or less, more preferably 90 or less, further preferably 85 or less, and particularly preferably 80 or less.
[0187] It should be noted that the storage modulus at 25° C. (G′25), the storage modulus at 50° C. (G′25), and their ratio (G′25 / G′50) are measured by dynamic viscoelasticity measurement.
[0188] The adhesive layer A of the present invention may be a constituent member of an adhesive sheet (sometimes referred to as "adhesive sheet A" in this specification). That is, the adhesive sheet A is an adhesive sheet having at least one layer of adhesive layer A. It should be noted that the meaning of "adhesive sheet" includes "adhesive tape". That is, the adhesive sheet A may be an adhesive tape having a tape-like shape.
[0189] The adhesive sheet A may be a single-sided adhesive sheet in which only one side of the sheet is the surface of the adhesive layer (adhesive surface) (i.e., the surface of the adhesive layer A), or a double-sided adhesive sheet in which both sides of the sheet are the surfaces of the adhesive layer. The adhesive sheet A is not particularly limited, but from the perspective of being used for bonding between adherends, it is preferably a double-sided adhesive sheet, and more preferably a double-sided adhesive sheet in which both sides of the sheet are the surfaces of the adhesive layer A.
[0190] The adhesive sheet A may be an adhesive sheet without a substrate (substrate layer), a so-called "substrate-free" adhesive sheet (sometimes referred to as a "substrate-free adhesive sheet"), or an adhesive sheet with a substrate (sometimes referred to as an "adhesive sheet with a substrate"). As the above-mentioned substrate-free adhesive sheet, for example, a double-sided adhesive sheet formed only by the adhesive layer A, a double-sided adhesive sheet formed by the adhesive layer A and an adhesive layer other than the adhesive layer A (sometimes referred to as "other adhesive layers"), etc. As the above-mentioned adhesive sheet with a substrate, for example, a single-sided adhesive sheet having an adhesive layer A on one side of the substrate, a double-sided adhesive sheet having an adhesive layer A on both sides of the substrate, a double-sided adhesive sheet having an adhesive layer A on one single side of the substrate and other adhesive layers on the other single side, etc.
[0191] Among the above, from the perspective of improving optical properties such as transparency, a substrate-free adhesive sheet is preferred, and a double-sided adhesive sheet (substrate-free double-sided adhesive sheet) having no substrate and formed only by the adhesive layer A is more preferred. In addition, when the adhesive sheet A is an adhesive sheet having a substrate, it is not particularly limited, but from the perspective of processability, a double-sided adhesive sheet having an adhesive layer A on both sides of the substrate (a double-sided adhesive sheet with a substrate) is preferred.
[0192] It should be noted that the above-mentioned "substrate (substrate layer)" refers to the part that is adhered to the adherend together with the adhesive layer when the adhesive sheet A is used (pasted) on the adherend (optical component, etc.), and does not include the peeling film (release film) that will be peeled off when the adhesive sheet is used (pasted).
[0193] Adhesive sheet A can be an adhesive sheet with a substrate based on the above description. As such a substrate, for example, various optical films such as plastic film, anti-reflection (AR) film, polarizing plate, phase difference plate can be cited. As the raw materials of the above-mentioned plastic film, for example, polyester resins such as polyethylene terephthalate (PET), acrylic resins such as polymethyl methacrylate (PMMA), polycarbonate, triacetyl cellulose (TAC), polysulfone, polyarylate, polyimide, polyvinyl chloride, polyvinyl acetate, polyethylene, polypropylene, ethylene-propylene copolymer, plastic materials such as cyclic olefin polymers such as trade name "ARTON" (cyclic olefin polymer, manufactured by JSR Co., Ltd.), trade name "ZEONOR" (cyclic olefin polymer, manufactured by ZEON CORPORATION). It should be noted that these plastic materials can be used alone or in combination of two or more. In addition, the above-mentioned "substrate" refers to the part that is attached to the adherend together with the adhesive layer when the adhesive sheet is attached to the adherend (optical component, etc.). The release film (release film) that is peeled off when the pressure-sensitive adhesive sheet is used (when pasted) is not included in the "base material".
[0194] The substrate is preferably transparent. The total light transmittance of the substrate in the visible light wavelength region (according to JIS K7361-1) is not particularly limited, but is preferably 85% or more, and more preferably 88% or more. In addition, the haze of the substrate (according to JIS K 7136) is not particularly limited, but is preferably 1.5% or less, and more preferably 1.0% or less. Examples of such transparent substrates include PET films, non-oriented films such as "ARTON" and "ZEONOR".
[0195] The thickness of the substrate is not particularly limited, but is preferably 12 to 75 μm. It should be noted that the substrate may have any form of a single layer or a multilayer. In addition, the surface of the substrate may be subjected to a known and commonly used surface treatment such as a physical treatment such as a corona discharge treatment, a plasma treatment, or a chemical treatment such as a primer treatment.
[0196] The adhesive sheet A may have other adhesive layers (adhesive layers other than the adhesive layer A). The other adhesive layers are not particularly limited, and examples thereof include adhesive layers formed of commonly known adhesives such as urethane adhesives, acrylic adhesives, rubber adhesives, silicone adhesives, polyester adhesives, polyamide adhesives, epoxy adhesives, vinyl alkyl ether adhesives, and fluorine adhesives. It should be noted that the above adhesives may be used alone or in combination of two or more.
[0197] The pressure-sensitive adhesive sheet A may have other layers (eg, an intermediate layer, a primer layer, etc.) in addition to the pressure-sensitive adhesive layer A, other pressure-sensitive adhesive layers, and a substrate, within a range that does not impair the effects of the present invention.
[0198] Adhesive sheet A can be provided with a release film (release film) on the adhesive surface until use. There is no particular limitation on the form in which the adhesive surface of the optical adhesive sheet A is protected by a release film. It can be a form in which each adhesive surface is protected by two release films, or it can be a form in which each adhesive surface is protected by a release film with both sides as release surfaces by winding into a roll. The release film is used as a protective material for the adhesive layer and is peeled off when it is attached to the adherend. It should be noted that in the adhesive sheet A, the release film also serves as a support for the adhesive layer. It should be noted that the release film is not necessarily provided.
[0199] Known and commonly used methods can be used as a method for producing the pressure-sensitive adhesive sheet A. The method for producing the pressure-sensitive adhesive sheet A varies depending on the composition of the pressure-sensitive adhesive layer A, and is not particularly limited. For example, the following methods (1) to (3) can be used.
[0200] (1) An optical adhesive composition A containing a (meth)acrylic block copolymer A, a colorant, a silane coupling agent as needed, other additives, etc. is applied (coated) on a substrate or a separator and cured (eg, thermally cured) to produce an adhesive sheet A.
[0201] (2) An optical adhesive composition A (solution) prepared by dissolving the (meth)acrylic block copolymer A, a colorant, and optional additives in a solvent is applied (coated) onto a substrate or a separator, and dried and / or cured to produce an adhesive sheet.
[0202] (3) The pressure-sensitive adhesive sheet A produced in the above (1) is further dried.
[0203] The pressure-sensitive adhesive sheet A is not particularly limited, but is preferably a pressure-sensitive adhesive sheet produced by a heat-based curing reaction of the optical pressure-sensitive adhesive composition A containing a (meth)acrylic block copolymer A and a polymerization initiator (polymerization initiator such as a thermal polymerization initiator) from the viewpoint of productivity.
[0204] The thickness (total thickness) of the adhesive sheet A is not particularly limited, but is preferably 10 μm to 1 mm, more preferably 100 to 500 μm, and further preferably 150 to 350 μm. By making the thickness above 10 μm or more, the adhesive layer becomes easy to follow the height difference portion, and the height difference absorption can be improved. It should be noted that the thickness of the adhesive sheet A does not include the thickness of the release film.
[0205] Since the pressure-sensitive adhesive sheet A includes the pressure-sensitive adhesive layer A, it has excellent processability at room temperature.
[0206] In addition, the adhesive sheet A has an excellent level difference absorption property in a region exceeding 50°C because it has the adhesive layer A. For example, in addition to the level difference of 5 to 10 μm, the level difference absorption property is also excellent for a high level difference exceeding 40 μm. Furthermore, the level difference absorption property is also excellent for a high level difference exceeding 80 μm.
[0207] Furthermore, since the pressure-sensitive adhesive sheet A includes the pressure-sensitive adhesive layer A, it is excellent in adhesion reliability.
[0208] [Optical laminate]
[0209] The optical laminate according to the third aspect of the present invention includes a substrate and an adhesive layer (A). Figures 2 to 4 Schematic diagram (cross-sectional view) showing one embodiment of the optical layered body according to the third aspect of the present invention. Figure 2 In the embodiment, the optical laminate 20 has a laminated structure in which a substrate 1 and an adhesive layer 2 (adhesive layer A) are laminated. Figure 3In the optical laminate 21, the surface 1a of the substrate 1 on which the pressure-sensitive adhesive layer 2 is not laminated is subjected to an antireflection treatment and / or an antiglare treatment 3. Figure 4 In the optical laminate 22 , the surface 1 a of the substrate 1 on which the pressure-sensitive adhesive layer 2 is not laminated is provided with an anti-glare layer 3 a as an anti-reflection treatment and / or an anti-glare treatment.
[0210] According to the optical laminate of this embodiment, the aforementioned adhesive layer 2 becomes a sealing material for sealing the light-emitting elements arranged on the display panel, and the aforementioned substrate 1 becomes the outermost covering component. Therefore, there is no need to stack the covering component separately after sealing, which can reduce the number of processes and necessary components and improve manufacturing efficiency.
[0211] <Base Material>
[0212] In the present embodiment, there is no particular limitation on the substrate 1, and for example, glass, transparent plastic film substrates, etc. can be cited. There is no particular limitation on the aforementioned transparent plastic film substrate, and preferably a substrate with excellent visible light transmittance and excellent transparency (preferably a substrate with a haze value of less than 5%) can be cited. For example, a transparent plastic film substrate described in Japanese Patent Gazette No. 2008-90263 can be cited. As the aforementioned transparent plastic film substrate, a substrate with less optical birefringence can be appropriately used. In the present embodiment, the substrate 1 can also be used as a covering member of a self-luminous display device, for example. In this case, as the aforementioned transparent plastic film substrate, a film formed by triacetyl cellulose (TAC), polycarbonate, acrylic polymer, polyolefin having a cyclic or norbornene structure, etc. is preferably used. In addition, in the present embodiment, the substrate 1 can be the aforementioned covering member itself. If this scheme is used, the process of stacking the covering member separately can be reduced in the manufacture of the self-luminous display device, thereby reducing the number of processes and necessary components, and improving production efficiency can be achieved. In addition, if this scheme is used, the aforementioned covering member can be further thinned. It should be noted that, when the substrate 1 is a covering component, the surface 1a that has been subjected to anti-reflection treatment and / or anti-glare treatment constitutes the outermost surface of the self-luminous display device, and plays the following roles: preventing the reduction in visibility caused by reflection of external light, image reflection, etc., and adjusting aesthetics such as glossiness.
[0213] In the present embodiment, there is no particular limitation on the thickness of the substrate 1. For example, in consideration of strength, operability and thinness, the thickness is preferably in the range of 10 to 500 μm, more preferably in the range of 20 to 300 μm, and most preferably in the range of 30 to 200 μm. There is no particular limitation on the refractive index of the substrate 1. For example, it is in the range of 1.30 to 1.80, preferably in the range of 1.40 to 1.70. There is no particular limitation on the visible light transmittance of the substrate 1. For example, it is 85 to 100%, and can be 88% or more, 90% or more, or 92% or more.
[0214] In this embodiment, it is preferred that the surface 1a of the substrate 1 is subjected to a reflective surface treatment and / or an anti-glare treatment 3. When the surface 1a of the substrate 1 is subjected to a reflective surface treatment and / or an anti-glare treatment 3, the surface 1a becomes the outermost surface of the self-luminous display device, and can prevent the reduction of visibility caused by reflection of external light, image reflection, etc., or can adjust the aesthetics such as glossiness. The anti-glare treatment is preferably easy to manufacture and low in cost.
[0215] As the aforementioned anti-reflection (AR) treatment, a known AR treatment can be applied without particular limitation. Specifically, it can be implemented by forming an anti-reflection layer (AR layer) obtained by stacking two or more layers of optical thin films or the aforementioned optical thin films with strictly controlled thickness and refractive index on a single surface 1a of the substrate 1. The aforementioned AR layer exhibits an anti-reflection function by utilizing the interference effect of light to cancel out the reversed phases of the incident light and the reflected light. The wavelength region of visible light that exhibits the anti-reflection function is, for example, 380 to 780 nm, and the wavelength region with high visual sensitivity is in the range of 450 to 650 nm. It is preferred to design the AR layer in such a way that the reflectivity of its central wavelength of 550 nm is minimized.
[0216] As the aforementioned AR layer, a multilayer antireflection layer having a structure of stacking two or five optical thin layers (thin films with strictly controlled thickness and refractive index) can be generally cited. By forming multiple layers with components having different refractive indices at a predetermined thickness, the freedom of optical design of the AR layer is increased, the antireflection effect can be further improved, and the spectral reflection characteristics can be made uniform (flat) in the visible light region. In the aforementioned optical thin film, since high thickness accuracy is required, the formation of each layer is generally implemented by vacuum evaporation, sputtering, CVD, etc., which belong to dry methods.
[0217] As the anti-glare (AG) treatment, a known AG treatment can be applied without particular limitation, and for example, the AG treatment can be performed by forming an anti-glare layer on one surface 1 a of the substrate 1 . Figure 2 2 is a schematic diagram (cross-sectional view) showing another embodiment of the optical laminate of the first aspect of the present invention. In the optical laminate 22 of this embodiment, an anti-glare layer 3a is formed on a single surface 1a of the substrate 1. As the anti-glare layer 3a, a known anti-glare layer can be used without limitation, and is generally formed as a layer in which inorganic or organic particles as an anti-glare agent are dispersed in a resin.
[0218] In this embodiment, the anti-glare layer 3a is formed using an anti-glare layer forming material including a resin, particles, and a thixotropy imparting agent, and the particles and the thixotropy imparting agent are aggregated to form a convex portion on the surface of the anti-glare layer 3a. According to this scheme, the anti-glare layer 3a has excellent display characteristics that take into account both anti-glare properties and prevention of white blur, and although the anti-glare layer is formed by the aggregation of particles, the generation of protrusions on the surface of the anti-glare layer that become appearance defects can be prevented, thereby improving the yield rate of the product.
[0219] Examples of the resin include thermosetting resins and ionizing radiation curable resins that are cured by ultraviolet rays or light. Commercially available thermosetting resins, ultraviolet curable resins, and the like may also be used as the resin.
[0220] As the aforementioned thermosetting resin and ultraviolet curing resin, for example, a curing compound having at least one of acrylate and methacrylate groups that is cured by heat, light (ultraviolet rays, etc.) or electron beams, for example, can be used, and examples thereof include oligomers or prepolymers such as acrylates and methacrylates of multifunctional compounds such as silicone resins, polyester resins, polyether resins, epoxy resins, urethane resins, alkyd resins, spiroacetal resins, polybutadiene resins, polythiol polyene resins, and polyols. These can be used alone or in combination of two or more.
[0221] In the aforementioned resin, for example, a reactive diluent having at least one of an acrylate group and a methacrylate group can also be used. The aforementioned reactive diluent can be, for example, a reactive diluent recorded in Japanese Patent Publication No. 2008-88309, including, for example, monofunctional acrylates, monofunctional methacrylates, multifunctional acrylates, multifunctional methacrylates, etc. As the aforementioned reactive diluent, preferred are acrylates with more than three functions and methacrylates with more than three functions. This is because the hardness of the anti-glare layer 3a can be made excellent. As the aforementioned reactive diluent, for example, butanediol glycerol ether diacrylate, acrylates of isocyanuric acid, methacrylates of isocyanuric acid, etc. can also be listed. These can be used alone or in combination of two or more.
[0222] The particles used to form the anti-glare layer 3a are used to give anti-glare properties and control the haze value of the anti-glare layer 3a as the main function so that the surface of the formed anti-glare layer 3a is concave-convex. The haze value of the anti-glare layer 3a can be designed by controlling the refractive index difference between the aforementioned particles and the aforementioned resin. As the aforementioned particles, for example, there are inorganic particles and organic particles. There is no particular restriction on the aforementioned inorganic particles, for example, silicon oxide particles, titanium oxide particles, aluminum oxide particles, zinc oxide particles, tin oxide particles, calcium carbonate particles, barium sulfate particles, talc particles, kaolin particles, calcium sulfate particles, etc. In addition, there is no particular restriction on the aforementioned organic particles, for example, polymethyl methacrylate resin powder (PMMA particles), silicone resin powder, polystyrene resin powder, polycarbonate resin powder, acrylic styrene resin powder, benzoguanamine resin powder, melamine resin powder, polyolefin resin powder, polyester resin powder, polyamide resin powder, polyimide resin powder, polyvinyl fluoride resin powder, etc. These inorganic particles and organic particles may be used alone or in combination of two or more.
[0223] The weight average particle size (D) of the aforementioned particles is preferably in the range of 2.5 to 10 μm. By making the weight average particle size of the aforementioned particles in the aforementioned range, for example, the anti-glare property is better and white blur can be prevented. The weight average particle size of the aforementioned particles is more preferably in the range of 3 to 7 μm. It should be noted that the weight average particle size of the aforementioned particles can be measured, for example, using the Coulter counting method. For example, by using a particle size distribution measuring device using the pore resistance method (trade name: Coulter particle size analyzer, manufactured by Beckman Coulter, Inc.), the resistance of the electrolyte equivalent to the volume of the particles when the particles pass through the aforementioned pores is measured, thereby measuring the number and volume of the aforementioned particles and calculating the weight average particle size.
[0224] There is no particular limitation on the shape of the particles, and they may be, for example, roughly spherical beads or amorphous particles such as powders. They are preferably roughly spherical particles, more preferably roughly spherical particles with an aspect ratio of less than 1.5, and most preferably spherical particles.
[0225] The ratio of the particles in the anti-glare layer 3a is preferably in the range of 0.2 to 12 parts by weight, more preferably in the range of 0.5 to 12 parts by weight, and further preferably in the range of 1 to 7 parts by weight relative to 100 parts by weight of the resin. By setting the ratio in the above range, for example, the anti-glare property is more excellent and white blur can be prevented.
[0226] Examples of the thixotropy-imparting agent for forming the anti-glare layer 3 a include organoclay, oxidized polyolefin, and modified urea.
[0227] In order to improve the affinity with the resin, the organoclay is preferably an organically treated clay. Examples of the organoclay include layered organoclay. The organoclay may be prepared by itself or a commercially available product may be used. Examples of the commercially available products include LUCENTITE SAN, LUCENTITE STN, LUCENTITE SEN, LUCENTITE SPN, SOMASIF ME-100, SOMASIF MAE, SOMASIF MTE, SOMASIF MEE, and SOMASIF MPE (trade names, all manufactured by Co-op Chemical Co., Ltd.); S-BEN, S-BEN C, S-BEN E, S-BEN W, S-BENP, S-BEN WX, S-BEN N-400, S-BEN NX, S-BEN NX80, S-BEN NO12S, S-BEN NEZ, S-BEN NO12, S-BEN NE, S-BEN NZ, and S-BEN NZ70; ORGANITE, ORGANITE D, and ORGANITE T (trade names, all manufactured by HOJUN Co., Ltd.); KUNIPIA F, KUNIPIAG, KUNIPIAG4 (trade names, all manufactured by KUNIMINE INDUSTRIES CO., LTD.); TIXOGEL VZ, CLAYTONE HT, CLAYTONE 40 (trade names, all manufactured by Rockwood Additives Ltd.), etc.
[0228] The oxidized polyolefin may be prepared by itself or a commercial product may be used. Examples of the commercial product include DISPARLON 4200-20 (trade name, manufactured by Kusumoto Chemicals Co., Ltd.) and FLOWNON SA300 (trade name, manufactured by Kyoeisha Chemical Co., Ltd.).
[0229] The modified urea is a reaction product of an isocyanate monomer or an adduct thereof with an organic amine. The modified urea may be prepared by itself or a commercial product may be used. Examples of the commercial product include BYK410 (manufactured by BYK Chemie).
[0230] The thixotropy-imparting agent may be used alone or in combination of two or more.
[0231] In the optical laminate 22 of the present embodiment, it is preferred that the height of the convex portion from the roughness average line of the anti-glare layer 3a is less than 0.4 times the thickness of the anti-glare layer 3a. More preferably, it is in the range of 0.01 times or more and less than 0.4 times, and further preferably in the range of 0.01 times or more and less than 0.3 times. If it is in this range, it is possible to suitably prevent the formation of protrusions that become appearance defects on the convex portion. The anti-glare layer 3a of the present embodiment can make appearance defects less likely to occur by having a convex portion of such a height. Here, the height of the distance average line can be measured, for example, by the method described in Japanese Patent Gazette No. 2017-138620.
[0232] The ratio of the thixotropy-imparting agent in the anti-glare layer 3 a is preferably in the range of 0.1 to 5 parts by weight, more preferably in the range of 0.2 to 4 parts by weight, based on 100 parts by weight of the resin.
[0233] There is no particular restriction on the thickness (d) of the anti-glare layer 3a, and it is preferably in the range of 3 to 12 μm. By making the thickness (d) of the anti-glare layer 3a in the aforementioned range, for example, the optical laminate 22 can be prevented from curling, and problems such as poor transportability and reduced productivity can be avoided. In addition, when the aforementioned thickness (d) is in the aforementioned range, the weight average particle size (D) of the aforementioned particles is preferably in the range of 2.5 to 10 μm as described above. By making the thickness (d) of the anti-glare layer 3a and the weight average particle size (D) of the aforementioned particles the aforementioned combination, the anti-glare property can be made more excellent. The thickness (d) of the anti-glare layer 3a is more preferably in the range of 3 to 8 μm.
[0234] The relationship between the thickness (d) of the anti-glare layer 3a and the weight average particle size (D) of the aforementioned particles is preferably within the range of 0.3≤D / d≤0.9. By being in this relationship, the anti-glare property is more excellent, and white blur can be prevented, thereby forming an anti-glare layer without appearance defects.
[0235] As described above, the optical laminate 22 of the present embodiment is agglomerated by the aforementioned particles and the aforementioned thixotropy imparting agent, thereby forming a convex portion on the surface of the anti-glare layer 3a. At the aggregation portion where the aforementioned convex portion is formed, the aforementioned particles exist in a state of being aggregated in the surface direction of the anti-glare layer 3a. Thus, the aforementioned convex portion forms a smooth shape. The anti-glare layer 3a of the present embodiment can prevent white blur while maintaining anti-glare properties by having a convex portion of such a shape, thereby making it difficult for appearance defects to occur.
[0236] The surface shape of the anti-glare layer 3a can be arbitrarily designed by controlling the aggregation state of the particles contained in the anti-glare layer forming material. The aggregation state of the aforementioned particles can be controlled, for example, by the material of the aforementioned particles (e.g., the chemical modification state of the particle surface, affinity for solvents, resins, etc.), the type and combination of resins (binders) or solvents, etc. Here, the present embodiment can control the aggregation state of the aforementioned particles by the thixotropy imparting agent contained in the aforementioned anti-glare layer forming material. As a result, the present embodiment can make the aggregation state of the aforementioned particles as described above, and can make the aforementioned convex portion form a smooth shape.
[0237] In the optical laminate 22 of the present embodiment, when the substrate 1 is formed of a resin or the like, it is preferred to have a permeation layer at the interface between the substrate 1 and the anti-glare layer 3a. The permeation layer is formed by the resin component contained in the material forming the anti-glare layer 3a penetrating into the substrate 1. If a permeation layer is formed, the adhesion between the substrate 1 and the anti-glare layer 3a can be improved, which is preferred. The thickness of the permeation layer is preferably in the range of 0.2 to 3 μm, and more preferably in the range of 0.5 to 2 μm. For example, when the substrate 1 is triacetyl cellulose and the resin contained in the anti-glare layer 3a is an acrylic resin, the permeation layer can be formed. The permeation layer can be confirmed, for example, by observing the cross section of the optical laminate 22 with a transmission electron microscope (TEM), and the thickness can be measured.
[0238] Even when the present embodiment is applied to an optical laminate 22 having such a permeable layer, a desired smooth surface concavo-convex shape that takes into account both anti-glare properties and prevention of white blur can be easily formed. In the permeable layer, the more the substrate 1 lacks adhesion to the anti-glare layer 3a, the more preferably the substrate 1 is formed thicker in order to improve adhesion.
[0239] In this embodiment, it is preferred that the number of appearance defects with a maximum diameter of 200 μm or more be 1 m 2 The number of anti-glare layers 3a is 1 or less. It is more preferable that the aforementioned appearance defects are absent.
[0240] In the present embodiment, the substrate 1 formed with the anti-glare layer 3a preferably has a haze value in the range of 0 to 10%. The aforementioned haze value refers to the haze value (haze) according to JIS K 7136 (2000 edition). The aforementioned haze value is more preferably in the range of 0 to 5%, and further preferably in the range of 0 to 3%. In order to make the haze value in the above range, it is preferred to select the aforementioned particles and the aforementioned resin in such a way that the refractive index difference between the aforementioned particles and the aforementioned resin is in the range of 0.001 to 0.02. By making the haze value in the above range, a clear image can be obtained, and the contrast in a dark place can also be improved.
[0241] In the present embodiment, it is preferred that the average inclination angle θa (°) at the concavo-convex shape on the surface of the anti-glare layer 3a is in the range of 0.1 to 5.0, more preferably in the range of 0.3 to 4.5, further preferably in the range of 1.0 to 4.0, and particularly preferably in the range of 1.6 to 4.0. Here, the average inclination angle θa is a value defined by the following mathematical formula (1). The average inclination angle θa is, for example, a value measured by the method described in Japanese Patent Application Laid-Open No. 2017-138620.
[0242] Average inclination angle θa = tan-1Δa (1)
[0243] In the above mathematical formula (1), Δa is a value obtained by dividing the sum of the differences (height h) between the apex of adjacent hills and the lowest point of valleys in the reference length L of the roughness curve specified in JIS B 0601 (1994 edition) by the above reference length L, as shown in the following mathematical formula (2). The above roughness curve is a curve obtained by removing the surface waviness component longer than the specified wavelength from the cross-sectional curve using a phase difference compensation type high-pass filter. In addition, the above cross-sectional curve refers to: when the target surface is cut by a plane perpendicular to the target surface, the contour that appears at the cut.
[0244] Δa=(h1+h2+h3…+hn) / L (2)
[0245] When θa is within the above range, the anti-glare property is more excellent and white blurring can be prevented.
[0246] When forming the anti-glare layer 3 a , the prepared anti-glare layer forming material (coating liquid) preferably exhibits thixotropy, and the Ti value specified below is preferably in the range of 1.3 to 3.5, and more preferably in the range of 1.3 to 2.8.
[0247] Ti value = β1 / β2
[0248] Here, β1 is the viscosity measured at a shear rate of 20 (1 / s) using RheoStress 6000 manufactured by HAAKE, and β2 is the viscosity measured at a shear rate of 200 (1 / s) using RheoStress 6000 manufactured by HAAKE.
[0249] If the Ti value is less than 1.3, appearance defects are likely to occur, and anti-glare properties and white blur properties are deteriorated. In addition, if the Ti value exceeds 3.5, the particles are less likely to aggregate and are more likely to be dispersed.
[0250] There is no particular limitation on the method for manufacturing the anti-glare layer 3a of the present embodiment, and any method can be used for manufacturing. For example, an anti-glare layer forming material (coating liquid) containing the aforementioned resin, the aforementioned particles, the aforementioned thixotropy imparting agent, and a solvent can be prepared, and the aforementioned anti-glare layer forming material (coating liquid) is applied to the single side 1a of the aforementioned substrate 1 to form a coating film, and the aforementioned coating film is cured to form the anti-glare layer 3a, thereby manufacturing. In the present embodiment, a method of imparting a concave-convex shape by a transfer method based on a mold, sandblasting, an embossing roller, or the like can also be used in combination.
[0251] There is no particular limitation on the aforementioned solvent, and various solvents can be used, one alone or two or more in combination. The optimal solvent type and solvent ratio exist according to the composition of the aforementioned resin, the type and content of the aforementioned particles and the aforementioned thixotropy imparting agent. The solvent is not particularly limited, and examples thereof include: alcohols such as methanol, ethanol, isopropanol, butanol, and 2-methoxyethanol; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclopentanone; esters such as methyl acetate, ethyl acetate, and butyl acetate; ethers such as diisopropyl ether and propylene glycol monomethyl ether; glycols such as ethylene glycol and propylene glycol; cellosolves such as ethyl cellosolve and butyl cellosolve; aliphatic hydrocarbons such as hexane, heptane, and octane; aromatic hydrocarbons such as benzene, toluene, and xylene, and the like.
[0252] When the permeable layer is formed of triacetyl cellulose (TAC) as the substrate 1, a good solvent for TAC can be preferably used. Examples of the solvent include ethyl acetate, methyl ethyl ketone, and cyclopentanone.
[0253] In addition, by appropriately selecting a solvent, the thixotropy of the anti-glare layer forming material (coating liquid) brought about by the thixotropy imparting agent can be well demonstrated. For example, when using an organoclay, toluene and xylene can be used alone or in combination, for example, when using an oxidized polyolefin, methyl ethyl ketone, ethyl acetate, propylene glycol monomethyl ether can be used alone or in combination, and for example, when using modified urea, butyl acetate and methyl isobutyl ketone can be used alone or in combination.
[0254] Various leveling agents can be added to the aforementioned anti-glare layer forming material. As the aforementioned leveling agent, for the purpose of preventing uneven coating (uniformization of the coating surface), for example, a fluorine-based or silicone-based leveling agent can be used. In the present embodiment, the leveling agent can be appropriately selected according to the situation where the surface of the anti-glare layer 3a is required to be anti-fouling, or the situation where an anti-reflection layer (low refractive index layer) or a layer containing an interlayer filler is to be formed on the anti-glare layer 3a. The present embodiment, for example, enables the coating liquid to exhibit thixotropy by including the aforementioned thixotropy imparting agent, so uneven coating is not easily produced. Therefore, the present embodiment, for example, has the advantage of being able to expand the options of the aforementioned leveling agent.
[0255] The amount of the leveling agent blended is, for example, 5 parts by weight or less, and preferably in the range of 0.01 to 5 parts by weight, relative to 100 parts by weight of the resin.
[0256] The anti-glare layer forming material may be added with pigments, fillers, dispersants, plasticizers, ultraviolet absorbers, surfactants, antifouling agents, antioxidants, etc. as needed within a range that does not impair performance. These additives may be used alone or in combination of two or more.
[0257] For the anti-glare layer forming material, a conventionally known photopolymerization initiator as described in, for example, JP-A-2008-88309 can be used.
[0258] As a method for coating the anti-glare layer forming material on one side 1a of the substrate 1, for example, a coating method such as inkjet coating, die coating, spin coating, spray coating, gravure coating, roll coating, or bar coating can be used.
[0259] The anti-glare layer forming material is applied to form a coating on the substrate 1, and the coating is cured. The coating is preferably dried before curing. The drying may be, for example, natural drying, air drying, heating drying, or a combination of these methods.
[0260] There is no particular limitation on the curing method of the coating of the anti-glare layer forming material, but ultraviolet curing is preferred. The irradiation amount of the energy ray source is preferably 50 to 500 mJ / cm2 in terms of cumulative exposure at an ultraviolet wavelength of 365 nm. 2 If the irradiation dose is 50mJ / cm 2 If the curing temperature is 500 mJ / cm 2 The following can prevent the formed anti-glare layer from being colored.
[0261] As described above, the anti-glare layer 3a can be formed on the single side 1a of the substrate 1. It should be noted that the anti-glare layer 3a can also be formed by a manufacturing method other than the aforementioned method. Regarding the hardness of the anti-glare layer 3a of the present embodiment, although it is affected by the thickness of the layer in the pencil hardness, it is preferably 2H or more.
[0262] In this embodiment, the anti-glare layer 3a may be a multi-layer structure in which two or more layers are stacked.
[0263] In this embodiment, the AR layer (low refractive index layer) can be configured on the anti-glare layer 3a. For example, when the optical laminate 22 of this embodiment is installed in a self-luminous display device, one of the main factors that reduce the recognizability of the image can be listed as the reflection of light at the interface between the air and the anti-glare layer. The AR layer will reduce the surface reflection. It should be noted that the anti-glare layer 3a and the AR layer can be a multilayer structure with more than two layers stacked respectively.
[0264] In order to prevent the adhesion of contaminants and to improve the ease of removal of adhered contaminants, it is preferable to laminate an anti-contamination layer formed of a fluorine-containing silane compound or a fluorine-containing organic compound on the anti-glare layer 3 a .
[0265] In this embodiment, at least one of the substrate 1 and the anti-glare layer 3a is preferably surface treated. If the surface of the substrate 1 is surface treated, the adhesion with the anti-glare layer 3a is further improved. In addition, if the surface of the anti-glare layer 3a is surface treated, the adhesion with the aforementioned AR layer is further improved.
[0266] The other side of the anti-glare layer 3a may be subjected to solvent treatment to prevent the curling of the substrate 1. In addition, a transparent resin layer may be formed on the other side of the anti-glare layer 3a to prevent the curling.
[0267] In the present embodiment, the optical laminate 20 can be prepared by laminating the adhesive layer 2 on the surface 1b of the substrate 1. The optical laminate 21 can be prepared by laminating the adhesive layer 2 on the surface 1b of the substrate 1 that has not been subjected to the anti-reflection treatment and / or the anti-glare treatment. The optical laminate 22 can be prepared by laminating the adhesive layer 2 on the surface 1b of the substrate 1 on which the anti-glare layer 3a is not formed.
[0268] The method for laminating the adhesive layer 2 on the surface 1b of the substrate 1 is not particularly limited, and for example, the adhesive layer 2 may be laminated on the surface 1b of the substrate 1. Figure 1 The pressure-sensitive adhesive layer 2 shown is performed by peeling off one of the release films S1 and S2 and then laminating the peeled film onto the surface 1 b of the substrate 1 .
[0269] The thickness of the peeling film S1 may be the same as or different from the thickness of another peeling film S2. The peeling force when peeling the peeling film S1 may be the same as or different from the peeling force when peeling the peeling film S2. When the peeling forces of the two are different, the optical laminate having the adhesive layer 2 of the present embodiment can be prepared by first peeling the peeling film (light peeling film) with relatively small peeling force from the adhesive layer 2 and laminating it on the surface 1b of the substrate 1.
[0270] The optical laminate of this embodiment can also be produced by coating the optical adhesive composition A on the surface 1b of the substrate 1, forming the sheet, and, after heating and drying, attaching a release film to the surface of the coating film as needed.
[0271] As described above, the adhesive layer 2 containing the colorant has light absorption for visible light. The total light transmittance of the optical laminate of this embodiment is, for example, 80% or less, and can be 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, 20% or less, 10% or less, or 5% or less.
[0272] The optical laminate of the present embodiment may be provided with a release film on the adhesive layer until use. In addition, the optical laminate of the present embodiment may be laminated with a surface protection film on the surface 1a of the substrate 1 where the adhesive layer 2 is not laminated (when the surface 1a is subjected to anti-reflection treatment and / or anti-glare treatment, it is the treated surface). The surface protection film is suitable in the following aspects: preventing damage and dirt from attaching during the manufacture, transportation, and shipment of the aforementioned optical laminate and the optical product containing the same.
[0273] The optical laminate of this embodiment may have, in addition to the substrate 1, the adhesive layer 2 (adhesive layer A), the release film, and the surface protection film, other layers on the surface or between any layers, such as a substrate other than the substrate 1, an adhesive layer other than the adhesive layer 2, an intermediate layer, a primer layer, etc., within the range that does not impair the effects of the present invention.
[0274] <Self-luminous display device>
[0275] The self-luminous display device of the fourth aspect of the present invention is a display device that arranges a large number of tiny light-emitting elements on a wiring substrate, and uses a light-emitting control means connected thereto to selectively emit light from each light-emitting element, thereby being able to directly display visual information such as text, images, and videos on a display screen by using the flickering of each light-emitting element. As self-luminous display devices, there can be listed: Mini / Micro LED display devices, organic EL (electroluminescent) display devices. The optical laminate of the third aspect of the present invention is particularly suitable for use in the manufacture of Mini / Micro LED display devices.
[0276] Figures 5 to 7 It is a schematic diagram (cross-sectional view) showing an embodiment of a self-luminous display device (Mini / Micro LED display device) according to the fourth aspect of the present invention.
[0277] exist Figure 5In the present invention, the self-luminous display device (Mini / Micro LED display device) 30 includes: a display panel on which a plurality of LED chips 6 are arranged on a single surface of a substrate 4, and an optical laminate 20 according to the third aspect of the present invention. The surface on which the LED chips 6 are arranged on the display panel is laminated with the adhesive layer 2 of the optical laminate 20. Figure 6 In the self-luminous display device (Mini / Micro LED display device) 31, anti-reflection treatment and / or anti-glare treatment 3 are implemented on the surface 1a of the self-luminous display device (Mini / Micro LED display device) 30. Figure 7 In the self-luminous display device (Mini / Micro LED display device) 32, an anti-glare layer 3a is formed on the surface 1a of the self-luminous display device (Mini / Micro LED display device) 30 as an anti-reflection treatment and / or anti-glare treatment.
[0278] In this embodiment, a metal wiring layer 5 for sending a light control signal to each LED chip 6 is stacked on the substrate 4 of the display panel. Each LED chip 6 that emits light of each color of red (R), green (G), and blue (B) is alternately arranged on the substrate 4 of the display panel via the metal wiring layer 5. The metal wiring layer 5 is formed of a metal such as copper, which reflects the light emitted by each LED chip 6, reducing the image recognition. In addition, the light emitted by each LED chip 6 of each color of RGB will be mixed, and the contrast will be reduced.
[0279] In the Mini / Micro LED display device of the present embodiment, each LED chip 6 arranged on the display panel is encapsulated by the adhesive layer 2. Since the adhesive layer 2 is formed by an optical adhesive composition A containing a (meth) acrylic block copolymer A, the storage modulus is reduced in the region exceeding 50°C, forming high fluidity, and can fully follow the fine height difference between the LED chips 6 and encapsulate without gaps. In addition, near room temperature (e.g., 25°C), it shows a high storage modulus, is hard, and has good processability.
[0280] In addition, since the adhesive layer 2 contains a colorant, it has sufficient light-shielding properties in the visible light region. Since the fine height differences between the LED chips 6 are encapsulated without gaps using the adhesive layer 2 with high light-shielding properties, reflections caused by the metal wiring layer 5 can be prevented, color mixing between the LED chips 6 can be prevented, and contrast can be improved.
[0281] As described above, the optical laminate of the present embodiment can prevent the reflection and gloss of the metal surface even when a metal adherend is laminated on the adhesive layer because the adhesive layer contains a colorant. The reflectivity of the visible light region of 5° regular reflection of the substrate surface 1a when a metal adherend is laminated on the adhesive layer of the optical laminate of the present embodiment is preferably 50% or less, more preferably 30% or less, further preferably 15% or less, and particularly preferably 10% or less. The glossiness of the substrate surface 1a when a metal adherend is laminated on the adhesive layer of the optical laminate of the present embodiment (based on JIS Z8741-1997) is preferably 100% or less, more preferably 80% or less, further preferably 60% or less, and particularly preferably 50% or less.
[0282] In addition, copper, aluminum, stainless steel, etc. can be used as the above-mentioned metal adherend.
[0283] In the Mini / Micro LED display device 31 of the present embodiment, the surface 1a of the substrate 1 is subjected to an anti-reflection treatment and / or an anti-glare treatment 3 to prevent the substrate surface 1a from being reduced in visibility due to reflection of external light, image reflection, etc., or to adjust aesthetics such as glossiness. In addition, in the Mini / Micro LED display device 32 of the present embodiment, an anti-glare treatment 3a is formed on the surface 1a of the substrate 1 to prevent the substrate surface 1a from being reduced in visibility due to reflection of external light, image reflection, etc., or to adjust aesthetics such as glossiness. The average inclination angle θa (°) of the anti-glare layer 3a of the Mini / Micro LED display device 32 of the present embodiment is the same as described above.
[0284] The self-luminous display device of this embodiment may have optical components other than the display panel and the optical laminate. The above-mentioned optical components are not particularly limited, and examples thereof include: polarizing plates, phase difference plates, anti-reflection films, viewing angle adjustment films, optical compensation films, etc. It should be noted that the optical components also include components (decorative films, decorative films, surface protection plates, etc.) that perform the functions of decoration and protection while maintaining the recognizability of the display device and the input device.
[0285] The Mini / Micro LED display device of the present embodiment can be produced by bonding a display panel having a plurality of LED chips arranged on one surface of a substrate to the pressure-sensitive adhesive layer 2 of the optical laminate of the third aspect of the present invention.
[0286] The pasting of the optical laminate having a display panel and an adhesive layer is preferably carried out by lamination under heating and / or pressure. Specifically, the above-mentioned lamination is preferably carried out by heating and pressurizing at a temperature of 50°C or above. By heating and pressurizing at a temperature of 50°C or above, the adhesive layer forms high fluidity, which can fully follow the height difference of the LED chips arranged on the substrate and fit tightly without gaps. The heating is carried out at a temperature of 50°C or above, preferably at a temperature of 60°C or above, and more preferably at a temperature of 70°C or above. There is no particular limitation on the pressurization, for example, it is carried out at a temperature of 1.5 atm or above, preferably at a temperature of 2 atm or above, and more preferably at a temperature of 3 atm or above. Heating and pressurizing can be carried out, for example, using an autoclave or the like. After the Mini / Micro LED display device manufactured in this way is restored to room temperature (25°C), the storage modulus of the adhesive layer increases, and the processability and bonding reliability are improved.
[0287] Example
[0288] Hereinafter, the present invention will be described in more detail based on examples, but the present invention is not limited to these examples. It should be noted that various properties in the following production examples were evaluated or measured by the following methods.
[0289] (Surface shape measurement)
[0290] A glass plate (thickness 1.3 mm) manufactured by Matsunami Glass Industry Co., Ltd. was bonded to the surface of the anti-glare film where the anti-glare layer was not formed using an adhesive, and the surface shape of the anti-glare layer was measured using a high-precision fine shape measuring instrument (trade name; Surfcorder ET4000, manufactured by Kosaka Laboratory Co., Ltd.) under the condition of a cutoff value of 0.8 mm to obtain the average inclination angle θa. It should be noted that the high-precision fine shape measuring instrument automatically calculates the average inclination angle θa. The average inclination angle θa is based on JIS B 0601 (1994 edition).
[0291] (Haze)
[0292] The haze value was measured by the method specified in JIS K 7136, with the haze meter (manufactured by Murakami Color Research Laboratory Co., Ltd., trade name "HN-150") set so that light entered from the anti-glare surface of the anti-glare film.
[0293] (Visible light transmittance of adhesive sheet)
[0294] The release film on one side is peeled off from the adhesive sheet, and the alkali-free glass is bonded to the exposed surface. Then, the release film on the other side is peeled off from the adhesive sheet to obtain a sample with an adhesive sheet bonded to the alkali-free glass plate. Using this sample, the transmission spectrum of the evaluation sample is measured using a visible-ultraviolet spectrophotometer (manufactured by Hitachi High-Technologies Corporation, trade name "U-4100"). Using alkali-free glass (single substance) as the baseline, the ratio of the transmittance (amount of transmitted light) of the evaluation sample to the transmittance (amount of transmitted light) of the alkali-free glass is used as the transmittance of the adhesive sheet. Based on the transmission spectrum of the adhesive sheet, the transmittance T at a wavelength of 550nm is calculated. VIS .
[0295] (Visible light transmittance of anti-glare film)
[0296] The anti-glare film was placed in a spectrophotometer U4100 (manufactured by Hitachi High-Technologies Corporation) so that light was incident from the anti-glare layer side, and the transmittance (%) in the visible light region was measured. The transmittance is the Y value measured using a 2 degree viewing field (C light source) of JIS Z 8701 and corrected for visual sensitivity.
[0297] Production Example 1
[0298] (Preparation of Anti-glare Film)
[0299] As the resin contained in the anti-glare layer, 100 parts by weight of an ultraviolet curable urethane acrylate resin (manufactured by DIC Corporation, trade name "UNIDIC 17-806", solid content 80%) was prepared. With respect to 100 parts by weight of the resin solid content of the above resin, 14 parts by weight of styrene crosslinked particles (manufactured by Soken Chemical Co., Ltd., trade name "MX-350H", weight average particle size: 3.5 μm, refractive index 1.59) as light diffusing fine particles, 2.5 parts by weight of synthetic montmorillonite belonging to organic clay (manufactured by Kunimine Industries Co., Ltd., trade name "Sumecton San") as a thixotropic agent, 5 parts by weight of a photopolymerization initiator (manufactured by BASF, trade name "OMNIRAD907"), and 0.5 parts by weight of a leveling agent (manufactured by DIC Corporation, trade name "MEGAFAC F-556", solid content 100%) were mixed. The mixture was diluted with a toluene / ethyl acetate mixed solvent (weight ratio: 90 / 10) to a solid content concentration of 30% by weight to prepare a light diffusing element forming material (coating liquid).
[0300] On one side of a triacetyl cellulose (TAC) film (manufactured by Fujifilm Co., Ltd., product name "TG60UL", thickness: 60 μm) that can function as a protective layer, an anti-glare layer forming material (coating liquid) is applied using a rod coater to form a coating. Then, the transparent TAC film substrate formed with the coating is transported to a drying process. In the drying process, the coating is dried by heating at 110°C for 1 minute. Then, a high-pressure mercury lamp is used to irradiate the substrate with a cumulative light intensity of 300 mJ / cm 2 The coating was cured by ultraviolet light, and a light diffusion element with a thickness of 5.0 μm was formed on one side of the TAC film to obtain an anti-glare film 1. The haze value of the anti-glare film 1 was 42%. The θa (°) of the anti-glare layer of the anti-glare film 1 was 1.22. The visible light transmittance of the anti-glare film 1 was 90%.
[0301] Production Example 2
[0302] (Preparation of Anti-glare Film)
[0303] As light diffusing fine particles, 14 parts by weight of amorphous silica (manufactured by Fuji Silysia Chemical Ltd., trade name "SYLOPHOBIC 100", weight average particle size: 2.6 μm) was added to make the thickness after curing treatment 7.0 μm, and a light diffusing element was formed on one side of the TAC film by the same method as in Manufacturing Example 1 to obtain an anti-glare film 2. The haze value of the anti-glare film 2 was 11%. The θa (°) of the anti-glare layer of the anti-glare film 2 was 1.43. The visible light transmittance of the anti-glare film 2 was 91%.
[0304] Production Example 3
[0305] (Preparation of Anti-glare Film)
[0306] As the resin contained in the anti-glare layer forming material, 100 parts by weight of ultraviolet curing urethane acrylate resin (manufactured by DIC Corporation, trade name "UNIDIC 17-806", solid content 80%) was prepared. With respect to 100 parts by weight of the resin solid content of the above resin, 7 parts by weight of amorphous silica (manufactured by Fuji Silysiachemical Ltd., trade name "SYLOPHOBIC 702"), 6.5 parts by weight of amorphous silica (manufactured by Fuji Silysiachemical Ltd., trade name "SYLOPHOBIC 100"), 5 parts by weight of a photopolymerization initiator (manufactured by BASF, trade name "OMNIRAD184"), and 0.5 parts by weight of a leveling agent (manufactured by DIC Corporation, trade name "MEGAFAC F-556") were mixed as anti-glare layer forming particles. The mixture was diluted with toluene to a solid content concentration of 30% to prepare an anti-glare layer forming material (coating liquid).
[0307] As a light-transmitting substrate, a transparent plastic film substrate (TAC film, manufactured by Fuji Film Co., Ltd., trade name "TD80UL", thickness: 80 μm) is prepared. The anti-glare layer forming material (coating liquid) is formed into a coating film on one side of the transparent plastic film substrate using a rod coater. Then, the transparent plastic film substrate with the coating film formed is transported to a drying process. In the drying process, the coating film is dried by heating at 110°C for 1 minute. Then, a high-pressure mercury lamp is used to irradiate with a cumulative light amount of 300 mJ / cm 2 The coating film was cured by ultraviolet light to form an anti-glare layer with a thickness of 5.0 μm, thereby obtaining an anti-glare film 3. The θa (°) of the anti-glare layer of the anti-glare film 3 was 3.5. The visible light transmittance of the anti-glare film 3 was 91%.
[0308] Production Example 4
[0309] (Preparation of Anti-glare Film)
[0310] As anti-glare layer forming particles, 6.5 parts by weight of amorphous silica (manufactured by Fuji Silysia Chemical Ltd., trade name "SYLOPHOBIC 702"), 6.5 parts by weight of amorphous silica (manufactured by Fuji Silysia Chemical Ltd., trade name "SYLOPHOBIC 200"), and 2.5 parts by weight of a thickener (manufactured by Co-op Chemical Co., Ltd., trade name "LUCENTITE SAN") were added, and the thickness after curing was 8.0 μm. Anti-glare film 4 was obtained in the same manner as in Preparation Example 3. The θa (°) of the anti-glare layer of anti-glare film 4 was 2.3. The visible light transmittance of anti-glare film 4 was 91%.
[0311] Production Example 5
[0312] (Preparation of polymer RAFT solution A1)
[0313] Into a reaction container equipped with a condenser, a nitrogen inlet pipe, a thermometer and a stirring device, 50 parts by weight of cyclohexyl acrylate (CHA) as monomer components, 50 parts by weight of 3,3,5-trimethylcyclohexyl acrylate (TMCHA), 0.5 parts by weight of dibenzyl trithiocarbonate (DBTC) as a RAFT agent, and 100 parts by weight of ethyl acetate as a polymerization solvent were added, and 0.2 parts by weight of 2,2'-azobisisobutyronitrile (AIBN) as a thermal polymerization initiator was added, and solution polymerization was carried out under a nitrogen atmosphere, thereby obtaining a polymer RAFT solution A1 with a Mw of 180,000.
[0314] (Preparation of Adhesive Solution B1 Containing Acrylic Triblock Copolymer)
[0315] Into a reaction container equipped with a condenser, a nitrogen inlet pipe, a thermometer and a stirring device, 97 parts by weight of 2-ethylhexyl acrylate (2EHA) as monomer components, 3 parts by weight of 4-hydroxybutyl acrylate (4HBA), 100 parts by weight of the polymer RAFT solution A1 obtained above, and 100 parts by weight of ethyl acetate as a polymerization solvent were added, and 0.2 parts by weight of 2,2'-azobisisobutyronitrile (AIBN) as a thermal polymerization initiator was added, and solution polymerization was carried out under a nitrogen atmosphere, thereby obtaining an adhesive solution B1 containing an ABA type acrylic triblock copolymer having a Mw of 400,000 and a Mw / Mn of 4.3.
[0316] In the calculated glass transition temperature (Tg) based on the FOX formula, the Tg of segment A of the ABA type acrylic triblock copolymer was 32°C, and the Tg of segment B was -70°C.
[0317] The weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) of the above product were measured in terms of standard polystyrene by gel permeation chromatography (GCP method) under the following measurement conditions.
[0318] ·Measurement device: HLC-8320GPC (manufactured by Tosoh Corporation)
[0319] ·Chromatographic column: TSKgelGMH-H(S), (manufactured by Tosoh Corporation)
[0320] Mobile phase solvent: tetrahydrofuran
[0321] Flow rate: 1.0cm 3 / min
[0322] Column temperature: 40℃
[0323] Production Example 6
[0324] (Polymerization of prepolymer)
[0325] Into a separable flask equipped with a thermometer, a stirrer, a reflux condenser, and a nitrogen inlet tube, 22 parts by weight of 2-ethylhexyl acrylate (2EHA), 60 parts by weight of lauryl acrylate (LA), 10 parts by weight of N-vinyl pyrrolidone (NVP), 8 parts by weight of 4-hydroxybutyl acrylate, and 0.1 parts by weight of IRGACURE 651 as a polymerization initiator were added, and nitrogen was introduced and nitrogen replacement was performed for about 1 hour while stirring. Then, the mixture was heated at 5 mW / cm 2 The polymer was irradiated with UVA to adjust the reaction rate to 5 to 15% to obtain an acrylic prepolymer solution.
[0326] (Preparation of Adhesive Composition)
[0327] To the acrylic prepolymer solution obtained above (so that the total amount of the prepolymer is 100 parts by weight), 37 parts by weight of 2-ethylhexyl acrylate (2EHA), 0.1 parts by weight of 1,6-hexanediol diacrylate (manufactured by Shin-Nakamura Chemical Co., Ltd., trade name "NK Ester A-HD-N") as a multifunctional monomer, 0.3 parts by weight of 3-glycidoxypropyltrimethoxysilane (manufactured by Shin-Etsu Silicone, trade name "KBM-403") as a silane coupling agent, and 0.1 parts of 2,2-dimethoxy-1,2-diphenylethane-1-one (manufactured by BASF, trade name "IRGACURE 651") as a photopolymerization initiator were added to prepare a photopolymerizable adhesive composition solution.
[0328] Example 1
[0329] (Preparation of black adhesive composition)
[0330] To the PSA solution B1 containing the acrylic triblock copolymer obtained in Preparation Example 5, 0.5 parts by weight of a black dye ("VALIFAST BLACK 3810" manufactured by ORIENT CHEMICAL INDUSTRIES CO., LTD.) was added based on 100 parts by weight of the total amount of monomers used in Preparation Example 5 to prepare a black solvent-based PSA composition solution 1.
[0331] (Preparation of Adhesive Sheet)
[0332] A 75 μm thick polyethylene terephthalate (PET) film ("DIAFOIL MRF75" manufactured by Mitsubishi Chemical Corporation) with a silicone release layer on the surface was used as a substrate, and the above-prepared black solvent-based adhesive composition solution 1 was applied to the substrate and dried at 130° C. for 3 minutes to form an adhesive layer with a thickness of 150 μm. A 75 μm thick PET film ("DIAFOIL MRE75" manufactured by Mitsubishi Chemical Corporation) with a silicone release treatment on one side was attached to the adhesive layer to obtain an adhesive sheet 1 with release films attached to both sides in the form of a substrate-free adhesive sheet.
[0333] The visible light transmittance of the pressure-sensitive adhesive sheet 1 is less than 1%.
[0334] (Preparation of optical laminate)
[0335] The adhesive surface exposed by peeling off one release film from the above-obtained adhesive sheet 1 cut into 20 mm×20 mm was attached to the center of a 45 mm×50 mm glass plate (visible light transmittance: 93%), thereby obtaining an optical laminate 1 consisting of glass plate / adhesive sheet 1 / release film.
[0336] Example 2
[0337] (Preparation of black adhesive composition)
[0338] A black solvent-based adhesive composition solution 2 was prepared in the same manner as in Example 1 except that 1.0 part by weight of a black dye ("VALIFAST BLACK 3810" manufactured by ORIENT CHEMICAL INDUSTRIES CO., LTD.) was added.
[0339] (Preparation of Adhesive Sheet)
[0340] The same procedure as in Example 1 was performed except that the black solvent-based PSA composition solution 2 prepared above was applied onto the substrate, thereby obtaining a PSA sheet 2 having release films attached to both surfaces in the form of a substrate-free PSA sheet.
[0341] The visible light transmittance of the pressure-sensitive adhesive sheet 2 is less than 1%.
[0342] (Preparation of optical laminate)
[0343] The same procedure as in Example 1 was carried out except that the pressure-sensitive adhesive sheet 2 obtained above was used to obtain an optical laminate 2 consisting of a glass plate / pressure-sensitive adhesive sheet 2 / release film.
[0344] Example 3
[0345] (Preparation of black adhesive composition)
[0346] A black solvent-based adhesive composition solution 3 was prepared in the same manner as in Example 1 except that 2.0 parts by weight of a black dye ("VALIFAST BLACK 3810" manufactured by ORIENT CHEMICAL INDUSTRIES CO., LTD.) was added.
[0347] (Preparation of Adhesive Sheet)
[0348] The same procedure as in Example 1 was performed except that the black solvent-based PSA composition solution 3 prepared above was applied onto the substrate, thereby obtaining a PSA sheet 3 having release films attached to both surfaces in the form of a substrate-free PSA sheet.
[0349] The visible light transmittance of the adhesive sheet 3 is less than 1%.
[0350] (Preparation of optical laminate)
[0351] The same procedure as in Example 1 was carried out except that the pressure-sensitive adhesive sheet 3 obtained above was used to obtain an optical laminate 3 consisting of a glass plate / pressure-sensitive adhesive sheet 3 / release film.
[0352] Comparative Example 1
[0353] (Preparation of Adhesive Sheet)
[0354] The same procedure as in Example 1 was followed except that the PSA solution B1 prepared in Production Example 5 was applied on the substrate instead of the black solvent-based PSA composition solution 1 to obtain a PSA sheet 4 having release films attached to both surfaces as a substrate-free PSA sheet.
[0355] The visible light transmittance of the adhesive sheet 4 was 90%.
[0356] (Preparation of optical laminate)
[0357] An optical laminate 4 consisting of glass plate / adhesive sheet 4 / release film was obtained in the same manner as in Example 1 except that the pressure-sensitive adhesive sheet 4 obtained above was used.
[0358] Comparative Example 2
[0359] (Preparation of Adhesive Sheet)
[0360] The photopolymerizable adhesive composition solution obtained in Manufacturing Example 6 was coated on a release-treated PET film (light release film) to a thickness of 150 μm after drying, and heated and dried to obtain an adhesive layer. Another PET film (heavy release film) was laminated on the adhesive layer to obtain a photocurable adhesive sheet with release films attached on both sides. A black light lamp (manufactured by Toshiba Corporation, trade name "FL15BL") was used from one side of the adhesive sheet to illuminate the adhesive sheet at an illumination of 5 mW / cm 2 、Accumulated light quantity 1300mJ / cm 2 Thus, a 150 μm thick adhesive sheet 5 was obtained in the form of a substrate-free adhesive sheet, in which the photo-crosslinkable adhesive as a cured product of the adhesive composition was sandwiched between the PET films (light release film and heavy release film).
[0361] The values of the illuminance of the black light lamp are measured by an industrial UV detector (manufactured by TOPCON CORPORATION, trade name: UVR-T1, light receiving unit model UD-T36) having a peak sensitivity wavelength of about 350 nm.
[0362] The visible light transmittance of the adhesive sheet 5 was 90%.
[0363] (Preparation of optical laminate)
[0364] The same procedure as in Example 1 was carried out except that the pressure-sensitive adhesive sheet 5 obtained above was used to obtain an optical laminate 5 consisting of a glass plate / pressure-sensitive adhesive sheet 5 / release film.
[0365] (evaluate)
[0366] The following evaluations were performed using the optical layered bodies obtained in the above Examples and Comparative Examples. The evaluation methods are shown below.
[0367] (1) Evaluation of height difference followability
[0368] (Production of uneven adherends)
[0369] After bonding the laminate of TAC film (thickness 60μm) and adhesive (thickness 20μm) to a 45mm×50mm glass plate, a CO2 laser (wavelength 10.6μm, laser diameter 0μm) was used to perform linear etching processing on the central 10mm×10mm range at a pitch of 150μm in the length direction and 225μm in the width direction, thereby obtaining an adherend A in which the TAC film and the adhesive layer were processed into a grid-like concave-convex shape.
[0370] The adherend A simulates an LED panel in which a plurality of LED chips are arranged on a substrate.
[0371] (Vacuum bonding)
[0372] Using a vacuum laminating apparatus (manufactured by Climb Products, SE340aaH), the adhesive surface exposed by peeling off the release films of the optical laminates 1 to 5 prepared in Examples 1 to 3 and Comparative Examples 1 and 2 was laminated to the processed surface of adherend A with an accuracy within the processing range that the adhesive sheet can completely cover the adherend A, thereby obtaining evaluation samples 1 to 5 consisting of glass plate / adhesive sheets 1 to 5 / adhesive sheet A, respectively.
[0373] (Evaluation of height difference followability)
[0374] In the evaluation samples 1 to 5, the height difference following property was evaluated by calculating the area of the white portion by photographing with a fixed-point camera, using the property that the processed portion of the adherend A appears transparent when the pressure-sensitive adhesive sheet successfully follows the uneven pattern, while the portion that fails to follow appears white.
[0375] Height difference tracking property (%) = 100 - {[Area of white part during evaluation] / [Area of white part before lamination = 1 cm 2 ]×100}
[0376] The step followability was measured at the post-autoclave stage (under the conditions of 50° C. and 0.5 MPa for 60 minutes).
[0377] (2) Visible light transmittance
[0378] The optical laminate obtained in the above-mentioned examples and comparative examples was placed in a spectrophotometer U4100 (manufactured by Hitachi High-Technologies Corporation) in a manner such that light was incident from the glass plate side, and the transmittance (%) in the visible light region was measured. The transmittance is the Y value measured using a 2 degree viewing field (C light source) of JIS Z 8701 and corrected for visual sensitivity. The results are shown in Table 1.
[0379] (3) Reflectivity
[0380] A plate obtained by laminating aluminum foil on a black acrylic plate was prepared. The adhesive surface exposed by peeling off the release film of the optical laminate obtained in the above-mentioned embodiment and comparative example was laminated on the aluminum foil side of the above-mentioned plate to prepare a sample. The obtained sample was set in a spectrophotometer U4100 (manufactured by Hitachi High-Technologies Corporation) in a manner that the anti-glare film / TAC film was located on the light source side, and the reflectivity (%) in the visible light region of 5° regular reflection was measured. The results are shown in Table 1.
[0381] [Table 1]
[0382] (Table 1)
[0383] Height difference tracking Transmittance Reflectivity Example 1 98% <1% 4% Example 2 98% <1% 4% Example 3 95% <1% 4% Comparative Example 1 90% 90% 72% Comparative Example 2 0% 90% 72%
[0384] (1) Storage modulus [G'25, G'50, G'25 / G'50] and peak temperature and maximum value of tanδ
[0385] For the adhesive sheets 1, 4 and 5 obtained in the above-mentioned Example 1 and Comparative Examples 1 and 2, the storage modulus (G'25) at 25°C, the storage modulus (G'50) at 50°C and their ratio (G'25 / G'50), the peak temperature and the maximum value of tan δ were measured or evaluated. The measurement or evaluation method is shown below. The results of the measurement or evaluation are shown in Table 2.
[0386] The storage modulus at 25° C. and 50° C. and the peak temperature and maximum value of tan δ were determined by dynamic viscoelasticity measurement.
[0387] A sample obtained by laminating a plurality of adhesive sheets to a thickness of about 1.5 mm was used as a test sample. The dynamic viscoelasticity measurement was performed using the Advanced Rheometric Expansion System (ARES) manufactured by Rheometric Scientific Inc. under the following conditions, and the storage modulus (G') at 25°C and 50°C was read from the measurement results. 25 , G' 50 ) and the peak temperature and maximum value of tanδ.
[0388] (Measurement conditions)
[0389] Deformation mode: Twist
[0390] Measuring frequency: 1Hz
[0391] Heating rate: 5℃ / min
[0392] Measuring temperature: -100~150℃
[0393] Shape: Parallel plate 8.0mmφ
[0394] [Table 2]
[0395] (Table 2)
[0396]
[0397] Example 4
[0398] (Preparation of optical laminate)
[0399] The adhesive surface exposed by peeling off the release film on one side of the adhesive sheet 1 obtained in Example 1 cut into 20 mm×20 mm is adhered to the central part of the surface of the anti-glare film 1 obtained in Manufacturing Example 1 cut into 45 mm×50 mm on which the anti-glare layer is not formed, thereby obtaining an optical laminate 6 consisting of anti-glare film 1 / adhesive sheet 1 / release film.
[0400] Embodiments 5 to 7
[0401] (Preparation of optical laminate)
[0402] Optical laminates 7 to 9 consisting of anti-glare films 2 to 4 / adhesive sheet 1 / release film were obtained in the same manner as in Example 4 except that the anti-glare films 2 to 4 obtained in Production Examples 2 to 4 were used instead of the anti-glare film 1.
[0403] Various modifications of the present invention will be described below.
[0404] [Supplementary Note 1] An optical adhesive composition, characterized in that the optical adhesive composition contains a (meth)acrylic block copolymer and a colorant,
[0405] The (meth)acrylic block copolymer comprises:
[0406] a high Tg segment having a glass transition temperature of 0°C or higher and 100°C or lower, and
[0407] A low Tg segment having a glass transition temperature of -100°C or higher and lower than 0°C,
[0408] The (meth)acrylic block copolymer has tan δ peaks in the region of 0°C or higher and in the region of lower than 0°C.
[0409] Here, the glass transition temperature is calculated using the FOX equation from the monomer component composition constituting each segment.
[0410] [Appendix 2] The optical adhesive composition according to Appendix 1, wherein the maximum value of tan δ in the region of 0° C. or higher is 0.5 to 3.0.
[0411] [Supplement 3] The optical adhesive composition according to Supplement 1 or 2, wherein the (meth)acrylic block copolymer is an ABA type triblock copolymer.
[0412] [Supplement 4] The optical adhesive composition according to Supplement 3, wherein in the ABA type triblock copolymer, the A segment is the high Tg segment, and the B segment is the low Tg segment.
[0413] [Appendix 5] The optical adhesive composition according to any one of Appendices 1 to 4, wherein the monomer component constituting the high Tg segment in the (meth)acrylic block copolymer contains at least one selected from the group consisting of (meth)acrylic acid alkyl esters having a linear alkyl group having 1 to 3 carbon atoms, (meth)acrylic acid alkyl esters having a branched alkyl group having 3 or 4 carbon atoms, and alicyclic monomers.
[0414] [Supplementary Note 6] The optical adhesive composition according to Supplementary Note 5, wherein the monomer component constituting the high Tg segment in the (meth)acrylic block copolymer contains an alkyl (meth)acrylate having a branched alkyl group having 3 or 4 carbon atoms.
[0415] [Appendix 7] The optical adhesive composition according to Appendix 5, wherein the alicyclic monomer contains a cycloalkyl (meth)acrylate having a cycloalkyl group having 4 to 10 carbon atoms which may have a substituent.
[0416] [Supplementary Note 8] An optical adhesive composition according to any one of Supplementary Notes 1 to 7, wherein the monomer component constituting the low Tg segment in the (meth)acrylic block copolymer contains at least one selected from the group consisting of (meth)acrylic acid alkyl esters having a linear or branched alkyl group having 4 to 18 carbon atoms and hydroxyl-containing monomers.
[0417] [Supplement 9] The optical adhesive composition according to any one of Supplements 1 to 8, which contains 1% by weight or more of a hydroxyl group-containing monomer relative to the total amount (100% by weight) of monomer components constituting the low Tg segment in the (meth)acrylic block copolymer.
[0418] [Appendix 10] The optical adhesive composition according to any one of Appendices 1 to 9, wherein the (meth)acrylic block copolymer has a weight average molecular weight of 200,000 or more.
[0419] [Appendix 11] The optical adhesive composition according to any one of Appendices 1 to 10, wherein the molecular weight distribution of the (meth)acrylic block copolymer is greater than 1 and 5 or less.
[0420] [Appendix 12] The optical adhesive composition according to any one of Appendices 1 to 11, wherein the ratio of the storage modulus at 25°C to the storage modulus at 50°C (storage modulus at 25°C / storage modulus at 50°C) is 3 or more.
[0421] [Appendix 13] The optical adhesive composition according to any one of Appendices 1 to 12, wherein the storage modulus at 25° C. is 1 MPa or more and the storage modulus at 50° C. is 0.5 MPa or less.
[0422] [Appendix 14] The optical adhesive composition according to any one of Appendices 1 to 13, wherein the maximum value of the transmittance of the colorant at a wavelength of 400 to 700 nm is 80% or less.
[0423] [Appendix 15] A pressure-sensitive adhesive layer formed from the optical pressure-sensitive adhesive composition according to any one of Appendices 1 to 14.
[0424] [Supplementary Note 16] An optical laminate comprising a substrate and the pressure-sensitive adhesive layer according to Supplementary Note 15.
[0425] [Supplement 17] The optical layered body according to Supplement 16, wherein the surface of the substrate on which the coating layer is not laminated is subjected to an anti-reflection treatment and / or an anti-glare treatment.
[0426] [Supplementary Note 18] The optical layered body according to Supplementary Note 17, wherein the anti-glare treatment is an anti-glare layer provided on one surface of the substrate.
[0427] [Supplementary Note 19] The optical laminate according to Supplementary Note 18, wherein the anti-glare layer is formed using an anti-glare layer forming material comprising a resin, particles and a thixotropy imparting agent,
[0428] The anti-glare layer has aggregated portions forming convex portions on the surface of the anti-glare layer due to the aggregation of the particles and the thixotropy-imparting agent.
[0429] [Supplementary Note 20] The optical layered body according to Supplementary Note 19, wherein the average inclination angle θa (°) of the convex portions on the surface of the anti-glare layer is in the range of 0.1 to 1.5.
[0430] [Appendix 21] The optical layered body according to any one of Appendices 16 to 20, further comprising a surface protection film laminated on the surface of the substrate on which the pressure-sensitive adhesive layer is not laminated.
[0431] [Supplementary Note 22] A self-luminous display device, the self-luminous display device comprising:
[0432] A display panel having a plurality of light emitting elements arranged on one surface of a substrate, and
[0433] The optical layered body according to any one of Supplementary Notes 16 to 21,
[0434] The surface of the display panel on which the light emitting elements are arranged is laminated on the pressure-sensitive adhesive layer of the optical laminate.
[0435] [Supplementary Note 23] The self-luminous display device according to Supplementary Note 22, wherein the display panel is an LED panel in which a plurality of LED chips are arranged on a single surface of a substrate.
[0436] Industrial Applicability
[0437] The optical adhesive composition and the optical laminate of the present invention are suitable for encapsulating light-emitting elements of self-luminous display devices such as Mini / Micro LEDs.
[0438] Description of Reference Numerals
[0439] 10 Adhesive layer (adhesive sheet)
[0440] 20, 21, 22 Optical laminate
[0441] 1. Substrate
[0442] 2 adhesive layers
[0443] S1, S2 peeling film
[0444] 3 Anti-reflective treatment and / or anti-glare treatment
[0445] 3a Anti-glare layer
[0446] 30, 31, 32 Self-luminous display devices (Mini / Micro LED display devices)
[0447] 4 substrates
[0448] 5 Metal wiring layers
[0449] 6. Light-emitting element (LED chip)
Claims
1. An optical laminate, characterized in that: Therefore, the optical laminate includes a substrate and an adhesive layer formed of an optical adhesive composition. The surface of the substrate on which the adhesive layer is not laminated is subjected to an anti-reflection treatment and / or an anti-glare treatment, The optical adhesive composition contains a (meth)acrylic block copolymer and a colorant. The (meth)acrylic block copolymer comprises: a high Tg segment having a glass transition temperature of 0°C or higher and 100°C or lower, and A low Tg segment having a glass transition temperature of -100°C or higher and lower than 0°C, The (meth)acrylic block copolymer has tan δ peaks in a region above 0° C. and in a region below 0° C., respectively. Here, the glass transition temperature is calculated using the FOX equation from the monomer component composition constituting each segment.
2. The optical layered body according to claim 1, wherein: The (meth)acrylic block copolymer is an ABA type triblock copolymer.
3. The optical laminate according to claim 2, wherein: In the ABA type triblock copolymer, segment A is the high Tg segment, and segment B is the low Tg segment.
4. The optical layered body according to any one of claims 1 to 3, wherein The monomer component constituting the high Tg segment in the (meth)acrylic block copolymer contains at least one selected from the group consisting of (meth)acrylic acid alkyl esters having a linear alkyl group with 1 to 3 carbon atoms, (meth)acrylic acid alkyl esters having a branched alkyl group with 3 or 4 carbon atoms, and alicyclic monomers.
5. The optical layered body according to claim 4, wherein: The monomer component constituting the high Tg segment in the (meth)acrylic block copolymer contains an alkyl (meth)acrylate having a branched alkyl group having 3 or 4 carbon atoms.
6. The optical layered body according to claim 4, wherein: The alicyclic monomer contains a cycloalkyl(meth)acrylate containing a cycloalkyl group having 4 to 10 carbon atoms which may have a substituent.
7. The optical layered body according to any one of claims 1 to 6, wherein The monomer component constituting the low Tg segment in the (meth)acrylic block copolymer contains at least one selected from the group consisting of (meth)acrylic acid alkyl esters having a linear or branched alkyl group having 4 to 18 carbon atoms and hydroxyl group-containing monomers.
8. The optical layered body according to any one of claims 1 to 7, wherein The (meth)acrylic block copolymer contains 1% by weight or more of a hydroxyl group-containing monomer based on the total amount (100% by weight) of monomer components constituting the low Tg segment.
9. The optical layered body according to any one of claims 1 to 8, wherein The (meth)acrylic block copolymer has a weight average molecular weight of 200,000 or more.
10. The optical layered body according to any one of claims 1 to 9, wherein The molecular weight distribution of the (meth)acrylic block copolymer is greater than 1 and 5 or less.
11. The optical layered body according to any one of claims 1 to 10, wherein The colorant has an average transmittance of 80% or less at a wavelength of 400 to 700 nm.
12. The optical layered body according to any one of claims 1 to 11, wherein The anti-glare treatment is an anti-glare layer provided on a single surface of the substrate.
13. The optical layered body according to claim 12, wherein: The anti-glare layer is formed using an anti-glare layer forming material including a resin, particles and a thixotropy imparting agent. The anti-glare layer has aggregated portions forming convex portions on the surface of the anti-glare layer due to the aggregation of the particles and the thixotropy-imparting agent.
14. The optical layered body according to claim 13, wherein: The average inclination angle θa (°) of the convex portions on the surface of the anti-glare layer is in the range of 0.1 to 1.
5. 15 . The optical layered body according to claim 1 , further comprising a surface protection film laminated on a surface of the substrate on which the pressure-sensitive adhesive layer is not laminated.
16. A self-luminous display device, comprising: A display panel having a plurality of light emitting elements arranged on one surface of a substrate, and The optical layered body according to any one of claims 1 to 15, The surface of the display panel on which the light emitting elements are arranged is laminated on the adhesive layer of the optical laminate.
17. The self-luminous display device according to claim 16, wherein: The display panel is an LED panel in which a plurality of LED chips are arranged on a single surface of a substrate.
Citation Information
Patent Citations
Cured coating film, Anti-reflection hard coating film using it, polarization plate and image display device
JP2008088309A
Antiglare hard coat film, manufacturing method of same, optical element, polarizing plate, and image display apparatus
JP2008090263A
Antiglare film, polarizing plate, image display apparatus, and method for manufacturing antiglare film
JP2017138620A
Light absorption layer contained in color filter for organic electroluminescence display and sheet using the same
JP2017203810A
display device
JP2018523854A